Breaking barriers in rice chlorophyll retrieval from satellite imagery: Mitigating row structure and saturation effects via RiceGORT and chlorophyll sensitivity enhancement - Haoran Sun; Hifza Mariam; Junnan She; Ming Chen; Dong Li; Chongya Jiang; Xia Yao; Iftikhar Ali; Yan Zhu; Weixing Cao; Tao Cheng (Remote Sensing of Environment, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

MDA5 associates with MAVS and its splicing variant in the antiviral response of large yellow croaker Larimichthys crocea - Ying Li; Yi Fan Zhang; Xia Ming Chen; Qiang Ma; Jiao Nan Zhang; Xiao Mei Huang; Jing Xuan Li; Yu Xuan Zhu; Tuan Yu Guo; Peng Fei Zou (Fish & Shellfish Immunology, 2026)

An enhanced SPH framework to simulate dynamic motion of soil-rock mixtures considering discontinuity contact - Chengzhi Xia; Zhenming Shi; Ming Peng; Jian He; Hang Li; Limin Zhang (Computers and Geotechnics, 2026)

Tuning morphology and oxygen vacancies in bio-templated TiO2 via precursor concentration for enhanced UV-activated room temperature NO2 sensing - Hong Li; Yi Xia; Li Yang; Qiuni Zhao; Ming Hou; Qingfu Dai; Jiabin Yang; Shenghui Guo (Chemical Engineering Journal, 2026)

Constructing Co-O-P bridging to induce spin state reconfiguration: In situ electro-oxidation of P for industrial-scale alkaline water electrolysis - Miao Ma; Chuan-De Qi; Qiao Xia; Qian-Xi Lv; Xin-Jie Tian; Man-Man Li; Sheng-Jun Xu; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2026)

Development of TM hypoallergenic enzymatic products with the potential to induce immune tolerance in Lateolabrax japonicus - Meng-Si Li; Qing-Mei Liu; Fei Xia; Su-Jie Huang; Shun-Xian Lin; Li-Qiang Zhong; Hao-Tian Zhang; Gui-Xia Chen; Guang-Ming Liu (Food Bioscience, 2026)

Thermal performance of a coupled thermal curtain and earth-air heat exchanger system for Chinese solar greenhouses in cold climates - Dapeng Sun; Changhua Tan; Shengli Li; Ming He; Tianyang Xia; Xingan Liu; Tianlai Li (Energy and Buildings, 2026)

Highly selective NO2 sensing for mobile on-site monitoring enabled by a dual-sensitization mechanism in palladium sulfide-based nanocomposites - Yongjing Guo; Hangshuo Feng; Qiuni Zhao; Shenghui Guo; Renminxi Ou; Shunping Zhang; Zaihua Duan; Yi Xia; Zhen Yuan; Ming Hou; Li Yang; Huiling Tai (Chemical Engineering Journal, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Advanced oxidation and reduction processes for degradation of refractory organic pollutants: Mechanisms, catalysts, and redox coupling strategies - Xiaoyu Zhang; Xia Li; Le Fang; Shaoqing Liu; Jie Tang; Yuan Gao; Danfeng Yu; Yudong Sun; Yun Wang; Ming Zhou; Cheng Zhang; Wei Ouyang (Chemical Engineering Journal, 2026)

Dynamics and drivers of CO2 emissions in agricultural river-ditch networks: management and wetland degradation effects - Xia Li; Xiao-Dong Li; Si-Liang Li; Shi-Yuan Ding; Wan-Fa Wang; Li Bai; Min Xiao; Ming-Guo Wang; Xiao-Long Liu (Applied Geochemistry, 2026)

Porous maghemite–sepiolite–silica xerogel sorbent for broad-spectrum removal of antibiotics, micro/nanoplastics and dye - Zhixin Xia; Jiajun He; U.T. Uthappa; Ming Zhang; Lipeng Liao; Zhuwen Liu; Xu Li; Qian Cheng; Zhiguang Guo; Ben Wang (Journal of Hazardous Materials, 2026)

Comparison of food allergic immune responses in sensitized female and male Balb/c mouse induced by Lateolabrax japonicus tropomyosin - Meng-Si Li; Qing-Mei Liu; Fei Xia; Li-Qiang Zhong; Zhi-Qiang Chen; Ya-Ping Wu; Yu-Ni Liao; Gui-Xia Chen; Yi-Xiang Liu; Guang-Ming Liu (Food and Chemical Toxicology, 2026)

A unified 3D SPH framework for simulating the landslide-damming-breaching-flood cascading hazards - Shuang Li; Ming Peng; Zhenming Shi; Hongchao Zheng; Chengzhi Xia; Maomao Liu; Yan Zhu (Engineering Geology, 2026)

Lignin-enabled versatile inks for DIW 3D-printing of soft materials - Xiran Lin; Haozhe Xia; Xiaohui Wu; Runguo Wang; Yanming Li; Ming Li; Hanjie Ying; Chenjie Zhu (Chemical Engineering Journal, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Enhanced water level fluctuations reduced the competitive advantage of cyanobacteria - Yan Chen; Rui Xia; Ruining Jia; Junde Ming; Kai Zhang; Jinghui Dou; Tianxiang Zhao; Xiang Li; Qin Zhang; Qi Zhang (Journal of Hydrology, 2026)

Effective photodynamic inactivation of curcumin in combination with ethylenediaminetetraacetic acid against Burkholderia gladioli pathovar cocovenenans - Xiu-Xia Tian; Jia-Jun Yan; Rui Huang; Quan Zhou; Qi-Ying Zeng; Yu-Ming Jiang; Zi-Hui Chen; Hai-Yan Wang; Bai-Sheng Li; Yong-Ning Wu; Wei-Liang Wu (Food Research International, 2026)

ANN-assisted interfacial engineering of MOFs heterostructures for synergistic CO2 photoreduction and antibiotic elimination - Fan Ye; Zhe Lin; Xu-Chao Xia; Ting Zou; Jin-Yu Dai; Lin Zhang; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2026)

Integrative multi-omics reveals NQO1-mediated airway epithelial injury as a key mechanism of bisphenol A–induced COPD - Rui Li; Shaobo Ge; Jin Liu; Yuer Li; Shiyuan Yao; Shuhan Ma; Yuanliang Sun; Xiao Li; Xia Yang; Jie Zhang; Ming Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Expression of Transforming Growth Factor Beta 1 in Lung Adenocarcinoma and Its Relationship with Circulating Tumour Cells - Ning Chen; Duo-Jun Qiu; Jian-Zhu Yang; Gui-Yun Zhu; Li-Fei Kang; Xiao-Ying An; Zhi-Ming Xu; Xiao-Xia Li (Biochemical Genetics, 2026)

Key Risk Factor Identification for Deep-Sea Transportation Safety Based on Complex Network Theory - Kun Lang; Xia Liu; Lin Li; Ming Zhong (Journal of Marine Science and Engineering, 2026)
Deep-sea transportation is faced with complex navigation environments, long voyages, limited emergency response resources, and interacting safety risks. Existing studies have mainly focused on individual risk factors, while the correlations and coupling effects among different factors have received insufficient attention. To identify the key risk factors affecting deep-sea transportation safety, this paper proposes a novel key factor identification model based on complex network theory. Firstly, 34 risk factors affecting deep-sea transportation safety are selected from five aspects using a literature analysis method. Secondly, a weighted directed network of risk factors is constructed based on complex network theory. Then, to evaluate the node importance, six node importance evaluation indicators are established, and a node importance evaluation method is proposed by integrating the analytic hierarchy process (AHP), technique for order preference by similarity to an ideal solution (TOPSIS), and gray relational analysis (GRA). Key risk factors are then determined according to the node importance evaluation results. Finally, the effectiveness of the proposed model is verified through a case study. The results show that the top five most critical risk factors are risk of leakage, emergency speed, physical and chemical properties of the cargoes, sense of personnel safety duty, and seasonal route. The findings can provide practical support for maritime authorities, shipping companies, and safety managers in formulating targeted prevention, control, and emergency response measures for deep-sea transportation safety.

Genome-wide analysis of the CHIA gene family and functional characterization of ScCHIA1 under cold and osmotic stress in jojoba (Simmondsia chinensis) - Xue Zhu; Ming Zhu; Luping Li; Ronghao Xia; Huini Xu; Fei Gao; Lamei Zheng (Plant Science, 2026)

Deep learning uncovers conserved regulatory logic and element dosage underlying stable gene expression in grasses - Jiacheng Li; Xinbing Xu; Chunjiao Xia; Yinmeng Liu; Luchang Ming; Wenhui Li; Yujian Yang; Weibo Xie (Molecular Plant, 2026)

Freeze-thaw cycles threaten high-altitude cold-region rock slopes stability: Advances in SPH simulation - Chengzhi Xia; Zhenming Shi; Hang Li; Ming Peng; Limin Zhang (International Journal of Rock Mechanics and Mining Sciences, 2026)

Investigating key free radical reactions and their impact mechanisms during coal spontaneous combustion - Junjie Qin; Lanjun Zhang; Xuyao Qi; Jinhu Li; Yang Wu; Yibo Zhao; Wenjing He; Ming Xia; Ying Wang (Fuel, 2026)

Deep learning and hyperspectral imaging for non-destructive amino acid detection in live carp fillets - Ying-jie Qi; Yi-Ming Cao; Yan Zhang; Qi Wang; Ran Zhao; Kai-Kuo Wang; Ying-Jie Chen; Xia-Jun Qi; Jiong-Tang Li (Food Research International, 2026)

A surface-engineered mycelial biofilm incorporating a self-cascading nanozyme for mycotoxin degradation in edible oils - Xue-ming Cao; Xue-ting Zhu; Yang-yang Geng; Ruo-mu Xia; Jin-min Zhang; Li-na Wu (Chemical Engineering Journal, 2026)

Homocysteine-induced bone formation dysfunction reversed by icariin via the AKT/FOXO1 signaling pathway - Suzhen Chao; Yunying Fu; Xinyi Peng; Yili Zhou; Junjie Xia; Ming Chen; Yang Li; Shengyuan Li; Min Shi; Xunli Xia; Bo Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Experimental study on the wave mitigation characteristics of a grid-type flexible-membrane breakwater under regular waves - Chuan-Rui Li; Jing-Ping Wu; Ming-Liang Cai; Jun-Ao Kang; Chang-Zhe Chen; Hong Fan; Chen-Xia Liu; Shi-Yu Yang; Zi-Wen Xu (Ocean Engineering, 2026)

Deep carbon recycling via the Tianshan basalt province and its contribution to Cenozoic elevated atmospheric CO2 concentration - Xiangsong Wang; Jinlong Yao; Guochun Zhao; Peter A. Cawood; Min Sun; Keda Cai; Xiao-Ping Xia; Pengfei Li; Xijun Liu; Ming Li; Yunying Zhang; Kai Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Pt decorated core-shell ZnS:Cu doped epoxy composites: Achieving enhanced breakdown strength and defect visualization - Zhi-Hao Xing; Ming-Xiao Zhu; Jian-Yi Xue; Jia Cheng; Guang Li; Bing Xia; Chongzi Cao; Yanbing Ji; Rui Liu (Chemical Engineering Journal, 2026)

New mesoporous UiO-66-OH framework with in-situ grown CsPbBr3 perovskite nanocrystals as a multifunctional sensor for the discrimination and instrument-free detection of three natural food additives - Hou-Qun Yuan; Qian-Wen Yang; Ling-Yi Guo; Yao-Hong Wang; Guan-Qun Li; Qiong-Yue Cui; Zhen-Chong Dou; Zhi-Qiang Cai; Yi-Fan Xia; Guang-Ming Bao (Chemical Engineering Journal, 2026)

Oxime ester–linked N-phenylphthalimide derivatives as PPO inhibitors: structure–activity relationships, herbicidal activity, crop selectivity, and in silico safety assessment - Xian-Ming Zhang; Yue-Li Zou; Ya Jiang; Si-Yi Yao; Shuang Gao; Li-Xia Zhao; Yu-Long Liu; Ying Fu (Pesticide Biochemistry and Physiology, 2026)

Outdoor thermal comfort of elderly people with musculoskeletal pain conditions in summer - Yaqian Deng; Chengxin Li; Weijie Xia; Yichun Cui; Ming Zhang; Kai Nan (Energy and Buildings, 2026)

Corrigendum to “Ultraviolet-induced Glycyrrhiza polysaccharide hydrogels with different mechanical strength for wound management” [Carbohydrate Polymers 374 (2026) 124712] - Zhuxian Wang; Ming Luo; Lehuan Ni; Yimeng Li; Dan Liu; Hongxia Zhu; Bijun Xia; Yuanyuan Liu; Qiang Liu; Bin Yang (Carbohydrate Polymers, 2026)

Quantitative reconstruction of the paleoclimate over the past 200 years in the northern margin of the east Asian summer monsoon, China - Yan-Xia Xue; Hong-Wei Meng; Yu-Zhen Ma; Chao Guo; Ting-Yong Li; Cai-Ming Shen (CATENA, 2026)

Berberine Hydrochloride Enhances the Fluconazole Susceptibility of Candida albicans through Multiple Targets - Lu Yu; Weijia Yi; Wenming Zheng; Dongming Zheng; Jiaqi Li; Lihua Luo; Guining Luo; Ming Xia; Li You; Jiangyan Yong (Current Microbiology, 2026)

Detecting extralateral mass variations using inclined satellite pair configurations - Tiantian Qing; Hao Zhou; Ming Li; Le Suo; Zhu Zhu; Mingyang Xia; Yaozong Li; Lijun Zheng; Shuyun Zheng; Siyou Xu; Zhicai Luo (Advances in Space Research, 2026)

Effects of Different Attractants on Growth, Antioxidant Capacity, and Feeding Gene Expression of Procambarus clarkii - Youhai Du; Silei Xia; Wuxiao Zhang; Wenping Yang; Yebing Yu; Zhaoxia Li; Bin Peng; Yude Wang; Bo Liu; Hongyan Tian; Jianhua Ming (Fishes, 2026)
The purpose of this study was to investigate the effects of different feeding-promoting substances added to high plant protein diets on the growth, antioxidant, serum biochemical parameters, immune, and feeding-related genes of Procambarus clarkii. A total of 450 crayfish (3.94 ± 0.03 g) were selected and randomly divided into six groups, with each group consisting of three replicates and 25 crayfish per replicate. The crayfish were fed a basal diet without attractant (control group) and five experimental diets supplemented with 0.4% betaine (BET), 0.4% trimetlylamine oxide (TMAO), 0.4% squid paste (SQU), 0.4% dimethyl-β-propiothetin (DMPT), and 0.4% taurine (TAU). The feeding trial lasted for 6 weeks. The results showed that compared with the control group, the BET, SQU, DMPT, and TAU groups significantly improved in growth performance, weight gain rate, and specific growth rate of crayfish. Compared with the control group, the BET, MTAO, and SQU groups significantly increased hepatopancreas SOD, CAT, and T-AOC. Histological results showed that compared with the control group, all feeding attractant groups could alleviate hepatopancreas tissue damage. Compared with the control group, the TMAO and SQU groups significantly reduced serum GLU content as well as ACP and AKP activities. The results of gene quantitative analysis showed that, compared with the control, TMAO significantly upregulated the expression of tlr, nf-kb, propo, hsp70, and tgf-β, while TAU significantly increased the expression of hsp70, hsp90 and nf-kb genes. Compared with the control group, the expression levels of tor, 4ebp1, and s6k1 in the TMAO group were significantly increased. Compared with the control group, the expression levels of leptin and npy genes in the DMPT group were significantly increased. In summary, the addition of attractants to high plant protein feed has the effects of promoting growth, enhancing antioxidant capacity, improving digestive enzyme activity, alleviating hepatopancreas injury, improving immunity, and promoting feeding.

Elucidating the molecular mechanism of pancreatic lipase inhibition by small molecules from Auricularia auricula-judae via integrated biophysical approaches - Xia Yin; Hui-Min Li; Jia-Yang Xu; Han Wu; Meng-Yue Dong; Ke-Ran Hao; Jin-Ming Gao (Food Bioscience, 2026)

Mitochondrial stress primed cGAS-STING activation synergized with NF-κB signaling for enhanced antitumor immunotherapy - Chengzhilin Li; Fanyu Yuan; LiHang Lou; Ziang Xu; Nianlei Zhang; Changshun Huang; Xinyu Wang; Wenyu Zhang; Tingjian Zu; Ming Xia; Runxiao Zheng (Chemical Engineering Journal, 2026)

Oxygen vacancy-engineered WO3 sensors with chemoselective gating for ultralow NO breathomics: Towards point-of-care asthma diagnostics - Renjie Chen; Renjun Si; Qingfu Dai; Li Yang; Ming Hou; Sufang He; Xiang Li; Shunping Zhang; Lan Xiang; Shenghui Guo; Yi Xia (Chemical Engineering Journal, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Effect of 6-Month High-Impact and Resistance Exercise on Regional Strength and BMD of Spine: A Clinical Trial Combined with a Finite-Element Study - Pu Duan; Yinxia Nie; Shizhong Liu; Xiaoyu Xia; Rui Xu; Simin Li; Vadim V. Silberschmidt; Lin Meng; Juan Du; Dong Ming (Annals of Biomedical Engineering, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Enhancing climate resilience of global dryland maize to cope with future 50-year climate warming - Jing Wang; Bao-Zhong Wang; Fei Mo; Yinglong Chen; Mohammad Ashraf; Yang Wang; Jian-Ming Li; Hai-Xia Duan; Yajie Song; Levis Kavagi; Hong-Yan Tao; You-Cai Xiong (Global Environmental Change, 2026)

Multidimensional analysis of the microbiota and fermentation quality of High-temperature Daqu from six distilleries in Guizhou Province - Yunxia Yang; Fengshuang Pan; Jianmeng Zhu; Ming Jiang; Chunhui Wei; Xuelian Huang; Xiangyong Zeng; Xia Liao; Wenying Fang; Shuyi Qiu; Dounan Li (Food Bioscience, 2026)

Petrogenesis and magmatic-hydrothermal evolution of the Dahongliutan pegmatite-type lithium deposit, Western Kunlun, NW China: A tourmaline perspective - Yong-Qi Xia; Ming-Jie Tuo; Nuerkanati Madayipu; Jianatiguli Wusiman; Dong-Mei Qi; Nuo Li (Lithos, 2026)

Evidence of heterogeneity in the mantle source of Quaternary Naozhou Island basalts from REEs and Sr-Nd-Pb isotopes - Cui Xiao-Ge; Li Zhi-Hua; Xie Shi-Xiong; Yang Wen-Jian; Wang Ming-Qiu; Cheng Liu-San; Gao Cai-Xia; Jiang Hong-Liang (Lithos, 2026)

Moss biocrusts enhance hydrological functionality on engineered slopes: pore restructuring, water retention, and hydrophobicity compensation in humid subtropical ecosystems - Chen Wang; Jiaqi Tan; Zhou Fang; Yingjie Zhang; Ming Luo; Binbin He; Shaoxian Song; Li Wu; María Luciana Montes; Delong Meng; Ling Xia (Journal of Hydrology, 2026)

Bell-shaped response of mercury methylation to sulfate loading in urban sewer systems: Implications for source-level control - Juntao Xia; Cheng Li; Yuming Zhen; Ming Liu; Jiahua Guo; Feng Jiang (Journal of Hazardous Materials, 2026)

Multiple resonance thermally activated delayed fluorescence emitters containing novel S-based acceptor with narrowed FWHM and enhanced EQE - Xiao-Xue Xia; Guo Yuan; Feng-Ming Xie; Qiang Zhang; Yan-Qing Li; Ze Hua; Jian-Xin Tang; Xin Zhao (Chemical Engineering Journal, 2026)

Ultraviolet-induced Glycyrrhiza polysaccharide hydrogels with different mechanical strength for wound management - Zhuxian Wang; Ming Luo; Lehuan Ni; Yimeng Li; Dan Liu; Hongxia Zhu; Bijun Xia; Yuanyuan Liu; Qiang Liu; Bin Yang (Carbohydrate Polymers, 2026)

Peroxymonosulfate-activated sludge conditioning coupled with membrane aerated biofilm reactor: mechanisms of extracellular polymeric substance reconfiguration, nitrogen metabolic shifts, and greenhouse gas mitigation - Jin Qi; Ming Li; Kai Zhu; Zongwei Xia; Lihua Huang; Haifeng Hao; Rujie Hao; Jun Liu (Bioresource Technology, 2026)

Drivers of soil carbon and nitrogen cycling during plantation succession: linking aboveground plant communities with belowground microbial networks - Xianghua Zuo; Wei Zhao; Jinying Li; Yunxiao He; Yueming Zhao; Ming Xing; Jiangnan Li; Xia Chen (Plant and Soil, 2026)

Plasma MicroRNA and Protein Signature Associated with Obesity in the Chinese Han Population Using MicroRNA Omics and Proteomics Analysis of 1026 Subjects - Yun-Xia Xie; Jian-Ge Qiu; Zhao-Hui Yang; Chen Ding; Le-Ming Shi; Si-Jia Wang; Li Jin; Bing-Hua Jiang (Phenomics, 2026)

13-cis-retinoic acid modulates porcine ovarian granulosa cell differentiation via retinoic acid signaling-FoxA1 axis: Implications for ovarian follicular development and luteinization - Hong-Liang Zhang; Hua-Biao Wang; Yi-Xuan Mi; Xia-Meng Wu; Li Bao; Ming Zhao; Li Ma; Shui-Lian Wang (Theriogenology, 2026)

Calcium-phosphate mediated green remediation of uranium mine water: sulfur-fixing ash enhanced phosphorus leaching from phosphogypsum for targeted uranium mineralization - Xue Xia; Ming Guo; Dan Chen; Yinyin Peng; Jialin Li; E. Li; Chunyan Ma; Xiaoqin Nie; Faqin Dong (Journal of Water Process Engineering, 2026)

Dicyanoisophorone-based near-infrared fluorescent probe with a large Stokes shift for the detection and bioimaging of hydrazine - Hong-Cheng Xia; Yu-Hang Zhang; Li-Ming Lv; Di Han; Hong-Kun Yang; Hui-Juan Yan; Jie-Li Lv; Jun-Tang Lin; Ying-Ying Kong (Journal of Hazardous Materials, 2026)

The gut as a reservoir of drug-resistant pathogens: Mechanisms of ENR-driven horizontal gene transfer in aquaculture - Bian-Hao Zeng; Ping Li; Hao-Ran Zhang; Bang-Hua Xia; Bin Liu; Ling-Ming Kong; Ling Liu; Zhi-Hua Li (Journal of Hazardous Materials, 2026)

Bacterial community in household municipal solid waste and bioaerosols released: Implications to health risks - Boning Kong; Shuang Li; Muhammad Asad; Yanqing Liu; Yuyang Long; Yan Zhao; Xia Huang; Ming Zhao; Wenjing Lu (Journal of Environmental Management, 2026)

Copper mediates oxidative stress and immune response in snakehead (Channa argus) through Nrf2 and NF-κB pathway - Xue-qin Wu; Ming-ze Li; Lu Lu; Xiu-mei Chen; Xiao-tian Niu; Yi-di Kong; Gui-qin Wang; Chang-ge Xia; Min Li (Fish & Shellfish Immunology, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

Dual-dynamic polyimide and its thermally conductive adhesive featuring high glass transition temperature, recyclability, and strong adhesion - Fang Li; Ping Yu; Bin Wu; Ming Cao; Ru Xia; Jiasheng Qian (Chemical Engineering Journal, 2026)

Self-amplifying tumor-targeting nanoreactor for enhanced Immuno-Ferroptosis therapy in triple-negative breast cancer - Jiayin Li; Yazhou Wang; Hao Li; Zhongyue Yuan; Qin Wei; Lei Yang; Yan-ming Xia; Xiaofei Xin; Lisha Liu; Chao Teng; Chao Qin; Xiaopeng Han; et al. (Chemical Engineering Journal, 2026)

Secondary metabolites from the arial parts of Hyssopus cuspidatus Boriss. and their chemotaxonomic significance - Jian-Kang Lu; Gui-Juan Zheng; Jing-Jing Li; Xiao-Xia Jiang; Jin-Xin Zhan; Chang-Hao Yu; Xu Wang; Yi-Xuan Zeng; Tian-Jiao Qi; Hong Liu; Hui-Ming Peng; Jin-Bo Fang (Biochemical Systematics and Ecology, 2026)

CDGSH Iron Sulfur Domain 1 Relieves Neuronal Ferroptosis via Activating AMPK Pathway in Alzheimer’s Disease - Yuanlong Li; Hua Fan; Xiong Han; Ming Ni; Xiaodan Hou; Hailan Xia; Yinzhu Shi; Lin Zhang; Jun Sun (Molecular Neurobiology, 2026)

RRBP1 Inhibition Reduces Microglial M1 Polarization and Inflammation-Mediated Neuronal Loss and Oxidative Stress by Regulating ERK Pathway in Alzheimer’s Disease - Yuanlong Li; Hua Fan; Xiong Han; Ming Ni; Xiaodan Hou; Hailan Xia; Yinzhu Shi; Lin Zhang; Jun Sun (Molecular Neurobiology, 2026)

Organic carbon facilitates the release of organic phosphorus by converting stable organic phosphorus into bioavailable forms in eutrophic sediments - Yan Wang; Xiang Chen; Cai Li; Ming Kong; Yan Tian; Xia Wang; Ying Ji; Lan Zhang; Xiaoshuai Hang (Journal of Environmental Sciences, 2025)

The variation of the East Asian summer monsoon on multi-centennial scale during 8.3–2.9 ka BP - Chao-Jun Chen; Ya-Xi Dong; Yao Wu; Jian Zhang; Hai-Bo Wang; Yan-Xia Xue; Wen-Jun Sun; Man-Ping Xie; Hai Cheng; Jun-Yun Li; Ming-Qiang Liang; Ting-Yong Li (Global and Planetary Change, 2025)

Ultra-permeable nanofiltration membranes with superior scaling and fouling resistance for petrochemical wastewater reclamation - Hao Guo; Mengxin Li; Zewen Xu; Zhicheng He; Jiawei Xia; Ming Wang; Deqing Shi; Xinliang Liu; Yingfei Hou (Chemical Engineering Journal, 2025)

Differentiation and trade-offs of root phosphorus acquisition strategies in different phosphorus efficiency genotypes of Chinese fir - Ming Li; Zhengying Cao; Xinyu Zhang; Fenglin Chen; Junjiao Ma; Zeqing Wang; Xia Hu; Pengfei Wu; Xiangqing Ma (Plant and Soil, 2025)

Conditional QTL/QTN mapping for seed width and mining candidate genes based on soybean FW-RIL population - Xu Wang; Bo Hu; Hong Xue; Ming Yuan; Quanzhong Dong; Wen-Xia Li; Zhimin Dong; Hailong Ning (Molecular Genetics and Genomics, 2025)

The formation and penetration characteristics of underwater shaped charge jets at varying depths: experiment, simulation, and machine learning - Chao Cao; Jingwen Xia; Kui Tang; Jinxiang Wang; Ming Yang; Yangchen Gu; Minhui Gu; Hanxin Gong; Yuanbo Li (Ocean Engineering, 2025)

Cyano cyclization-anchoring strategy breaks the activity-stability trade-off in COF photocatalysts - Xia-Jun Jin; Jing-Qi Liu; Hong-Xia Zhang; Qiang-Qiang Yu; Hong-Zhi Zhou; De-Ming Kong; Li-Na Zhu (Chemical Engineering Journal, 2025)

Design of EVOH nanofibers aerogel integrated with phase change materials for sustained solar-driven seawater desalination - Ye Zhang; Yi Wu; Shanshan Li; Mengqi Wang; Ke Liu; Ming Xia; Qin Cheng; Jia Xu; Shanshan He; Dong Wang (Chemical Engineering Journal, 2025)

Low-surface-energy polyfluorinated acceptors enable cascaded donor/acceptor distribution in ternary organic solar cells - Zhe Hao; Siyuan Li; Zhilong He; Ming Xia; Rongbin Zhang; Xuelin Wang; Zheng Tang; Hongliang Zhong (Chemical Engineering Journal, 2025)

Waste biomass-derived organic matter for sustainable soil remediation: Enhancing heavy metal removal and eluent reuse in agricultural application - Shuai Yang; Chen Tu; Guo-ming Liu; Yuan Li; Yi Wang; Xia Zhu; Shao-cheng Si; Run-lai Luo; Zhong-yuan Li; Yong-ming Luo (Bioresource Technology, 2025)

Hydrological variability significantly influences aquatic biological integrity at the spatial scale in semi-arid watersheds - Lina Li; Rui Xia; Xinghui Xia; Ming Dou; Minhua Ling; Yan Chen; Jinghui Dou; Kai Zhang; Ruining Jia; Chao Yan (Journal of Hydrology, 2025)

Unraveling the enrichment mechanisms of U, Re, Se and V in the Bayinqinggeli Deposit, Northern Ordos Basin through in situ mineralogical analysis - Xiao-Wen Hu; Ming-Xing Ling; Jian-Bing Xu; Fei Xia; De-Ru Xu; Ya-Lun Li; Xiao-Yong Yang; Chao Lu; Hua-Ming Li; Zhen-Cheng Li; Long-Hui Wang; Feng Zhang; et al. (Journal of Geochemical Exploration, 2025)

Nano architectonics via in situ growth of MIL-101(Fe) on modified sugarcane bagasse for selective capture of glyphosate from aqueous solution - Ru-yi Zhou; Ming-hua Liu; Yun Xiao; Yu Qin; Bo Zuo; Muhammad Akhtar Abbas; Jun-xia Yu; Xiao-di Li; Yue-fei Zhang; Ru-an Chi (Journal of Environmental Chemical Engineering, 2025)

A ratiometric fluorescent probe for sensitive detection of benzoyl peroxide and hypochlorite in food - Shun-Qiang Cui; Xin-Yi Liang; Zhi-Qiang Cai; Hou-Qun Yuan; Qiu-Yu Zhang; Yi-Fan Xia; A.K.I.M.A.N.A. Sandra; Ling-Yi Guo; Ran Wang; Shi-Yu Zhao; Yan-Xia Li; Guang-Ming Bao (Food Chemistry, 2025)

In/S co-decorated SnSe encapsulated in a dual carbon layer for sodium ion storage - Ya Ru Pei; Yong Jin Xia; Lei Ming Wang; Rui Li; Jun Xi Peng; Xue Jing Yang; Jian Li; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2025)

Moisture-adaptive cellulose/MXene aerogels for synergistic moisture and triboelectric energy harvesting - Jiwei Zhang; Xinran Zhou; Mengjie Wu; Liming Zhu; Zechang Ming; Weikang Li; Yong Xia; Hao Liu; Zijie Zhou; Tao Zhang; Minghui Fan; Jianyong Yu; et al. (Chemical Engineering Journal, 2025)

Optimizing electrochemical performance and temperature stability of NVPF via copper doping - Ramon Alberto Paredes Camacho; Xin-Yu Wang; Lei Shen; Qiang Wang; Yi-Ming Zhao; Ming-Xia Gao; Li Lu (Chemical Engineering Journal, 2025)

Upstream moisture sources and circulation patterns controls Asian monsoon hydroclimate over the past 20,000 years - Jian Zhang; Ming-Qiang Liang; Jun-Yun Li; Yao Wu; Yan-Xia Xue; Wen-Jun Sun; Xiang-Zhuo Liu; Jin-Ke Chen; Chao-Jun Chen; Ting-Yong Li (Quaternary Science Reviews, 2025)

Non-crystal freezing storage assisted by alternating electric field on fresh yak meat quality - Hengxun Lin; Yiping Yang; Qiuyao Xu; Yuan Li; Xiaojia Hu; Xia Li; Christophe Blecker; Guangyu Wu; Chuan Yang; Yanzhen Zhang; Ming Chi; Chunhui Zhang (Meat Science, 2025)

Epigenetic reprogramming of HDAC2 in CA1 excitatory neurons determines Pb-induced non-spatial memory deficits - Mengmeng Wang; Chengqing Huang; Shu Ai; Yanzhou Xia; Changqing Li; Yuxuan Zhi; Kun Wang; Ming Nie; Xiaozhen Gu; Yi Xu; Heyujia Zhang; Hui-Li Wang (Journal of Hazardous Materials, 2025)

Cross-reactivity and conserved epitope analysis of tropomyosin from Lateolabrax japonicus and shellfish species - Meng-Si Li; Fei Xia; Qing-Mei Liu; Fa-Jie Li; Yu-Ni Liao; Li-Qiang Zhong; Gui-Xia Chen; Lian-Zhong Luo; Yi-Xiang Liu; Guang-Ming Liu (Food Chemistry, 2025)

6,7-Dimethoxy-3H-Quinazolin-4-One as a dual-function inhibitor of polyphenol oxidase and bacteria: biological evaluation, mode of action, and anti-browning studies - Xiu-Zhen Li; Jin-Rui Qiao; Yi-Rui Wu; Dong-Yan Zhou; Yu-Dan Shi; Shu-Meng Zhu; Qiu-Han Bai; Xiao-Lei Xia; Wei-Ming Chai (Food Bioscience, 2025)

Role of circular RNAs in formaldehyde-induced lung Injury: Insights into expression and regulatory pathways - Pan Ge; Xiang Zhang; Yan-qi Yang; Jia-ming Xie; Mo-qi Lv; Ying Sun; Ya-zhao Li; Yuan-yuan Geng; Jian Zhang; Dang-xia Zhou (Food and Chemical Toxicology, 2025)

Corrigendum to “Zinc isotopic composition of oceanic crust: Insights from oceanic gabbro cumulates and MORBs” [Chemical Geology 670 (2024) 122443 1–13] - Xia Wang; Zaicong Wang; Jakub Ciazela; Zongqi Zou; Wei Li; Yuanyang Yu; Ming Li; Yongsheng Liu (Chemical Geology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

The ultrastructure of the Cretaceous feathers highlights the evolution of the feather - Jiajia Wang; Rui Qiu; Qian Chen; Di Liu; Tongbo Zhang; Ying Li; Xinjun Zhang; Baopeng Wang; Dongyu Hu; Dong Ren; Xiaolin Wang; Xiaofei Xia; et al. (Science Bulletin, 2025)

Strain-specific effects of fish originated Bacillus velezensis on growth, gut health, and disease resistance of zebrafish - Yuan-Yuan Yao; Wen-Hao Zhou; Juan Hu; Ya-Lin Yang; Ming Li; Rui Xia; Chao Ran; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Using the windmill-shaped array layout to realize the self-rolling propulsion of a multi-tentacled underwater robot - Zhihan Li; Ming Lei; Songlong Jiao; Han Yan; Yuyao Li; Dan Xia (Ocean Engineering, 2025)

A Hierarchical Reinforcement Learning Framework for Multi-Agent Cooperative Maneuver Interception in Dynamic Environments - Qinlong Huang; Yasong Luo; Zhong Liu; Jiawei Xia; Ming Chang; Jiaqi Li (Journal of Marine Science and Engineering, 2025)
To address the challenges of real-time decision-making and resource optimization in multi-agent cooperative interception tasks within dynamic environments, this paper proposes a hierarchical framework for reinforcement learning-based interception algorithm (HFRL-IA). By constructing a hierarchical Markov decision process (MDP) model based on dynamic game equilibrium theory, the complex interception task is decomposed into two hierarchically optimized stages: dynamic task allocation and distributed path planning. At the high level, a sequence-to-sequence reinforcement learning approach is employed to achieve dynamic bipartite graph matching, leveraging a graph neural network encoder–decoder architecture to handle dynamically expanding threat targets. At the low level, an improved prioritized experience replay multi-agent deep deterministic policy gradient algorithm (PER-MADDPG) is designed, integrating curriculum learning and prioritized experience replay mechanisms to effectively enhance the interception success rate against complex maneuvering targets. Extensive simulations in diverse scenarios and comparisons with conventional task assignment strategies demonstrate the superiority of the proposed algorithm. Taking a typical scenario of 10 agents intercepting as an example, the HFRL-IA algorithm achieves a 22.51% increase in training rewards compared to the traditional end-to-end MADDPG algorithm, and the interception success rate is improved by 26.37%. This study provides a new methodological framework for distributed cooperative decision-making in dynamic adversarial environments, with significant application potential in areas such as maritime multi-agent security defense and marine environment monitoring.

Numerical simulation of the effect of solar chimneys on NOx-O3 photochemical reaction and ventilation in urban street canyon - Hanbing Xiong; Tianhao Shi; Yongjia Wu; Ruiyue Xia; Xitong Yuan; Renaud de Richter; Wei Li; Yueping Fang; Nan Zhou; Wenyu Li; Chong Peng; Tingzhen Ming (Urban Climate, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Simultaneous and instrument-free detection of quinine and crystal violet based on a dual-emissive Eu3+-functionalized metal-organic framework - Hou-Qun Yuan; Yuan Yuan; Si-Yi Liu; Jia-Hao Fu; Yi-Fan Xia; Wei Li; Meng-Yuan Pan; Lirong Jiang; Peiyao Chen; Guang-Ming Bao (Journal of Hazardous Materials, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Engineering a thermophilic Bacillus thermoamylovorans for degradation of polyethylene terephthalate waste - Yi-Mei Cai; Cui-Can Lu; Tian-Tian Wang; Li-Jun Song; Yu-Ming Deng; Han Xu; Sheng Chen; Wei Xia; Jing Wu; Zheng-Fei Yan (Journal of Cleaner Production, 2025)

Exposure-effect of PFOS and PFOA on lung function: An integrated approach with epidemiological, cellular, and animal studies - Jia-Xin Zhou; Xiao-Di Qin; Xuan Liu; Wan-Ting He; Mohammed Zeeshan; Shyamali C. Dharmage; Jennifer Perret; Dinh Bui; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2025)

Extraction, characterization, and biological activities of a novel polysaccharide extract from Fructus caryophylli - Qingtao Yu; Wenzhi Li; Jieyi Long; Ming Liang; Lingli Jiang; Xiaoliang Lin; Dongqing He; Zhuoyan Wu; Xiaole Xia (Journal of Natural Medicines, 2025)

Petrogenesis of Early Permian within-plate-type gabbros in the Western Qiangtang Terrane, Tibet: partial melting of lithospheric mantle metasomatized by subducted oceanic sediments on the northern margin of the Gondwana - Xiao-Rui Fan; Yun-Chuan Zeng; Ji-Feng Xu; Feng Huang; Ming-Jian Li; Xi-Jun Liu; Hong-Xia Yu; Jing Hu (International Geology Review, 2025)

Intensified excessive wastage of key raw metals with expansion of global wind and solar photovoltaic energy development - Li He; Yun-Long Liu; Zhen-Jie Tang; Tong Sun; Yi-Ming Yan; Yong-Feng Xia; Hu-Shen Feng; Wei Ye (Resources, Conservation and Recycling, 2025)

Tumor cell-derived N-acetyl-aspartyl-glutamate reshapes the tumor microenvironment to facilitate breast cancer metastasis - Jie Xia; Lixing Zhang; Wucheng Zhu; Juchuanli Tu; Xilei Peng; Qiaodan Deng; Siqin Li; Xueyan He; Haonan Dong; Cuicui Liu; Xian Chen; Jiahui Xu; et al. (Science Bulletin, 2025)

Simultaneous recovery of water and antiscalant from cooling tower blowdown water by electrodialysis: Mechanism and cost-effectiveness - Jia-Rong Li; Jing-Han Wei; Yu-Chen Jin; Xian-Qiu Zhang; Hai-Ou Song; Ming-Xia Du (Journal of Cleaner Production, 2025)

Determination of the appropriate extraction method for bound aroma compounds from strawberry and analysis of aroma substances in strawberry fruits of different varieties and developmental stages - Li-Xia Sheng; Xiang-Rong Li; Xing-Ming Zhu; Hao Zhu; Jian-Qiang Yu (Food Chemistry, 2025)

Cobalt regulation biocathode with sulfate-reducing bacteria for enhancing the reduction of antimony and the removal of sulfate in a microbial electrolysis cell simultaneously - Yuchen Xie; Minhui Chen; Ming Yong; Zhuyuan Wang; Hongyu Wang; Ziyin Xia; Chenxi Li; Meng Li; Lei Huang; Jia Yan; Hongguo Zhang (Environmental Research, 2025)

Self-assembled gallic acid-rare earth nanocomplexes against MRSA with multi-targeting antibacterial mechanisms robustly combating bacterial resistance - Xian Liu; Qiwu Yuan; Yang Yang; Ke Li; Nanjiong Pang; Jiangtao Wang; Ming Yang; Xia Li; Junling Guo; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2025)

Phosphorus transformation after amendment applications in rapeseed soil with cadmium contamination - Zhuoqing Li; Yuexing Huang; Jiayi Wu; Boqing Tie; Xia Lu; Ming Lei; Xinqi Wang (Journal of Soils and Sediments, 2025)

Correction: Inhibition of 12/15 lipoxygenase by baicalein reduces myocardial ischemia/reperfusion injury via modulation of multiple signaling pathways - Lina Song; Hui Yang; Hong-Xia Wang; Cui Tian; Yu Liu; Xiang-Jun Zeng; Erhe Gao; Yu-Ming Kang; Jie Du; Hui-Hua Li (Apoptosis, 2025)

A novel nonlinear prestack inversion method based on nutcracker optimization algorithm with high convergence speed - Lin Zhou; Ming Ouyang; Jianping Liao; Jingye Li; Hanlin Xia; Haiyang Ding (Journal of Applied Geophysics, 2025)

Molecular basis of E93-dependent tissue morphogenesis and histolysis during insect metamorphosis - Mei Zeng; Zi-Yu Yan; Ya-Nan Lv; Jia-Ming Zeng; Ning Ban; Dong-Wei Yuan; Sheng Li; Yun-Xia Luan; Yu Bai (Insect Biochemistry and Molecular Biology, 2025)

The flotation deashing separation performance of high-ash fine coal-slime using humic acid depressant and insights to its depressant mechanism - Zili Yang; Yangchao Xia; Yanzhen Fu; Qinshan Liu; Ming Li; Xiahui Gui (Fuel, 2025)

Optimized carbonylation treatment of Litopenaeus vannamei matrix decreased its immunoreactivity and improved edible quality, simultaneously - Meng Liu; Ming-Xuan Wu; Fei-Fei Gong; Zhao-Min Sun; Ying Li; Fei Huan; Gui-Xia Chen; Qing-Mei Liu; Hong Liu; Guang-Ming Liu (Food Chemistry, 2025)

Automated nanoarchitectonics for networks filling by Prussian blue single crystals through an intermittentto-flow conversion - Zixuan Wan; Wei Zhang; Tianzi Li; Lingling Xia; Ruijuan Qi; Ming Hu (Chemical Engineering Journal, 2025)

Aristolochic acid I abnormally activates the wnt7b/β-catenin signaling pathway and affects the repair of renal tubules - Xiaofen Li; Ying Zhang; Ailin Lan; Maojuan Li; Ming Xia; Chuanhua Huang; Didong Lou (Chemico-Biological Interactions, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Maize kernel nutritional quality—an old challenge for modern breeders - Decui Li; Anqi Hao; Wen Shao; Weiwei Zhang; Fuchao Jiao; Haiyan Zhang; Xueyan Dong; Yuan Zhan; Xia Liu; Chunhua Mu; Zhaohua Ding; De Xue; et al. (Planta, 2025)

Effect of Maillard reaction on the allergenicity of crude extract of Mactra quadrangularis - Fa-Jie Li; Xin-Rong He; Dong-Xiao Li; Yang Yang; Shuai Kang; Qing-Mei Liu; Lian-Zhong Luo; Gui-Xia Chen; Guang-Ming Liu (Food Research International, 2025)

The impeded film-formation kinetics with ameliorated carrier trap density to construct efficient as-cast organic solar cells through short multi-branched alkylthio chains strategy - Ling Li; Na Li; Jiefeng Hai; Shenzheng Gao; Hao Xu; Ming Luo; Xinjie Zhou; Xiaoyu Shi; Shanlei Xu; Xueming Li; Zhenhuan Lu; Youyong Pang; et al. (Chemical Engineering Journal, 2025)

Roseobacter weihaiensis sp. nov., a cellulose-degrading bacterium isolated from intestinal content of Nipponacmea schrenckii collected from golden beach in Weihai, China - Yu-Rui Li; Ming-Jing Zhang; Yan-Jun Yi; Xiao-Chen Wang; Dong-Mei San; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2025)

Application of botulinum toxin A in tissue repair and regeneration - Xuan-Zhu Guo; Ya-Nan Niu; Xuan Zhou; Qiao Wei; Meng Li; Jia-Ning Xia; Yu-Qi Cui; Chao-Xin Chai; Yi-Ming Wang; Li-Ping Chen (Toxicon, 2024)

Polystyrene microplastics alleviate the developmental toxicity of silver nanoparticles in embryo-larval zebrafish (Danio rerio) at the transcriptomic level - Qiao-hong Xiao; Hao Xiang; Ya-nan Tian; Jiao-long Huang; Ming-qun Li; Pu-qing Wang; Kai Lian; Peng-xia Yu; Meng-yao Xu; Ruo-nan Zhang; Yan Zhang; Jie Huang; et al. (Science of The Total Environment, 2024)

Green fabrication of modified lignin/zeolite/chitosan-based composite membranes for preservation of perishable foods - Zhan-Chao Li; Meng-Yao Su; Xiao-Yu Yuan; Hai-Qing Lv; Rui Feng; Li-Jie Wu; Xiao-Ping Gao; Yan-Xia An; Zhan-Wei Li; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Chemistry, 2024)

Unlocking superior preservation: The synergy of lignin and zeolite in chitosan-based composite films for perishable foods - Zhan-Chao Li; Xi Chen; Jia-Li Zhang; Xiao-Ping Gao; Yan-Xia An; Li-Jie Wu; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Packaging and Shelf Life, 2024)

Self-delivered sonodynamic nanomedicine for enhanced tumor immunotherapy by simultaneously reversing the immunosuppression and immune resistance - Houyang Hu; Jie Yan; Haijun Zhu; Xuechun Wang; Yilei Zhao; Songyan Li; Zilin Ma; Fenglei Xu; Ming Xia; Jianwei Jiao; Miaoqing Zhao; Guiqiang Zhang (Chemical Engineering Journal, 2024)

A zircon petrochronologic perspective on raising the central Tibetan crust - Shu-Hui Ren; Yun-Chuan Zeng; Roberto Weinberg; Ji-Feng Xu; Jian-Lin Chen; Bao-Di Wang; Feng Huang; Xi-Jun Liu; Hong-Xia Yu; Ming-Jian Li (Chemical Geology, 2024)

Zinc isotopic composition of oceanic crust: Insights from oceanic gabbro cumulates and MORBs - Xia Wang; Zaicong Wang; Jakub Ciazela; Zongqi Zou; Wei Li; Yuanyang Yu; Ming Li; Yongsheng Liu (Chemical Geology, 2024)

A Protocol for Body MRI/CT and Extraction of Imaging-Derived Phenotypes (IDPs) from the China Phenobank Project - Chengyan Wang; Shuo Wang; Sha Hua; Ruokun Li; Yan Li; Zhang Shi; Kai Feng; Lizhen Lan; Meng Liu; Xutong Kuang; Xueqin Xia; Shihai Zhao; et al. (Phenomics, 2024)

Clostridium lamae sp. nov., a novel bacterium isolated from the fresh feces of alpaca - Xue Li; Ming Li; Weixiong Shi; Xia Li; Zhiguang Xiang; Lei Su (Antonie van Leeuwenhoek, 2024)

Recent selection and introgression facilitated high-altitude adaptation in cattle - Yang Lyu; Fuwen Wang; Haijian Cheng; Jing Han; Ruihua Dang; Xiaoting Xia; Hui Wang; Jincheng Zhong; Johannes A. Lenstra; Hucai Zhang; Jianlin Han; David E. MacHugh; et al. (Science Bulletin, 2024)

MGDA-assisted plant washing agent for improving the removal of Cd and Cu from farmland soils - Yi Wang; Chen Tu; Yuan Li; Shuai Yang; Ying Liu; Xia Zhu; Shao-cheng Si; Run-lai Luo; Xiang-liang Pan; Yong-ming Luo (Environmental Pollution, 2024)

A 3D SPH framework for simulating landslide dam breaches by coupling erosion and side slope failure - Shuang Li; Ming Peng; Liang Gao; Chengzhi Xia; Yan Zhu (Computers and Geotechnics, 2024)

“Balloon-like” biomimetic erythrocyte vesicles potentiate photodynamic therapy for inducing immunogenic cell death - Zhiyin Li; Yikang Ji; Yue Su; Zijie Zhou; Xia Yang; Yu Huang; Ming Yan; Lingyue Shen (Chemical Engineering Journal, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

ALKBH5 facilitates the progression of infantile hemangioma by increasing FOXF1 expression in a m6A-YTHDF2 dependent manner to activate HK-2 signaling - Kun Peng; Ren-Peng Xia; Fan Zhao; Yong Xiao; Ti-Dong Ma; Ming Li; Yong Feng; Chong-Gao Zhou (Molecular and Cellular Biochemistry, 2024)

Unified scheme design and control optimization of flapping wing for next-generation manta ray robot - Qi-meng Liu; Hao Chen; Peng-ming Guo; Guang-sheng Su; Wei-kun Li; Xin-yu Zeng; Di-xia Fan; Wei-cheng Cui (Ocean Engineering, 2024)

Dihydroartemisinin regulates the apoptosis and growth of colorectal cancer by suppressing DPYSL2 and increasing TF and ACHE - Xiao Zhang; Jun-Feng Cao; Dunshui Liao; Zengliang Xia; Li Xiong; Mei Wu; Chaochao Wang; Xingyu Yang; Yixin Qiu; Lixin Zhang; Ningbo Chen; Ming Zhang; et al. (Food Bioscience, 2024)

A wearable electrochemical sensor for the monitoring of neonicotinoid insecticides, salicylic acid and the pH in plant guttation - Guanglei Chu; Siping Yu; Yuhang Wang; Weifeng Zhang; Bing Xue; Jinqi Huang; Zhiwei Wang; Jianghe Luo; Xia Sun; Ming Li (Chemical Engineering Journal, 2024)

Paleozoic orogenic gold mineralization from metamorphism of volcanic sequences in the North Qinling terrane (central China): Insights from the Yindongpo gold deposit in the Tongbai area - Ming-Chun Chai; Jian-Wei Li; Ya-Fei Wu; Xiao-Ping Xia; Huai-Yu He; Wei Fu (Mineralium Deposita, 2024)

Summer sea ice melting enhances phytoplankton and dimethyl sulfide production - Cheng‐Xuan Li; Kan Chen; Xia Sun; Lu Liu; Ming Xin; Xuan‐Li Liu; Bao‐Dong Wang (Limnology and Oceanography, 2024)
The relationships among sea ice melting, phytoplankton assemblages, and the production of climate‐relevant trace gases in the Southern Ocean are gaining increasing attention from the scientific community. This is particularly true for dimethyl sulfide (DMS), which plays an important role in atmospheric chemistry by influencing the formation of sulfated aerosols with radiative impacts and constituting cloud condensation nuclei. In the current study, chlorophyll a (Chl a ), DMS and its precursors dimethylsulfoniopropionate (DMSP), were quantified in the Weddell–Scotia Confluence (WSC) during the 2018 record ice extent minimum period. Mixed layer changes were found to be generally associated with spatial variation in sea ice melt, with the depth being six times deeper in ice‐free, well‐mixed regions than in seasonal ice‐melting zones. The surface Chl a concentration increased from ice‐free to ice‐melting regions with elevated sea ice meltwater percentages and drawdown surface nutrient concentrations. The concentrations of surface and depth‐integrated Chl a in the upper 150 m reached maxima in the ice‐melting region with the highest fraction of sea ice meltwater, illustrating that sea ice melting promoted the occurrence of phytoplankton blooms. The DMS and DMSP concentrations in the vicinity of the ice‐melting zone were approximately three times higher than those in the ice‐free waters. The observations of this study show that the regions of ice melting in the WSC were a zone of particularly high sea–air fluxes of DMS, which could significantly contribute to the atmospheric budget of DMS in the polar regions.

Development of a multi-tentacled collaborative underwater robot with adjustable roll angle for each tentacle - Zhihan Li; Qingyuan Gai; Ming Lei; Han Yan; Dan Xia (Ocean Engineering, 2024)

Endoplasmic reticulum stress response modulator OsbZIP39 regulates cadmium accumulation via activating the expression of defensin-like gene OsCAL2 in rice - Jian Li; Ling-Yan Wang; Huan-Chao Huang; Wu Yang; Guang-Yi Dai; Zhi-Qiang Fang; Jun-Liang Zhao; Kuai-Fei Xia; Xuan Zeng; Meng-Ling He; Nan Yao; Ming-Yong Zhang (Journal of Hazardous Materials, 2024)

A facile and intelligent detection method for diclazuril based on a stable dual emissive Eu3+-dopped metal–organic framework - Yi-Fan Xia; Yan-Xia Li; Qing-Yan Xiao; Zhi-Qiang Cai; Qian-Wen Yang; Yi-Xuan Hu; Zi-Yi Mei; Guang-Ming Bao; Hou-Qun Yuan (Food Chemistry, 2024)

Carbon dots with tunable excitation-independent fluorescence and organelle-specific targeting via core graphitization and surface groups engineering - Ming-Yuan Sun; Bao-Hua Tian; Xin-Xin Li; Yu Li; Yu Lei; Xi-Lin Guo; Qiang Miao; Hao Li; Hai-Xia Liang (Chemical Engineering Journal, 2024)

Overexpression of the MiAGL1 gene from mango promoted flowering in transgenic Arabidopsis - Xue-mei Zeng; Xin-hua He; Wen-jing Mo; Hai-xia Yu; Ting-ting Lu; Li-ming Xia; Yi-li Zhang; Jia-wei Zhu; Cong Luo (Journal of Plant Biochemistry and Biotechnology, 2024)

Conformational transformation of activator strand directly regulates CRISPR/Cas12a system activity for live cell sensing of multiple biomolecules - Qing-Nan Li; Dong-Xia Wang; Zhi-Qi Dai; Shun-Li Wu; Gui-Mei Han; Sha Lu; Li-Na Zhu; Hong-Xin Jiang; De-Ming Kong (Chemical Engineering Journal, 2024)

Surface charge accumulation of functionalized carbonized polymer dots selectively induces lysosomal membrane permeabilization of breast cancer cells - Yu Lei; Bao-Hua Tian; Xin-Xin Li; Ming-Yuan Sun; Xi-Lin Guo; Yi-Da Wang; Hui-Qing Zhou; Ri-Sheng Ma; Hai-Xia Liang (Chemical Engineering Journal, 2024)

La promoted Ni0-Niδ+ synergistic interaction for rapid and deep hydrogenation of liquid organic hydrogen carriers - Ting Zhu; Li Liu; Yifang Zhao; Min Gao; Yuan Dong; Dong Xia; Peng Huang; Hansong Cheng; Ming Yang (Chemical Engineering Journal, 2024)

Sensitivity of atmospheric peroxyacetyl nitrate (PAN) formation and its impact on ozone pollution in a coastal city - Nan Fu; Li-Ming Cao; Shi-Yong Xia; Le-Wei Zeng; Li He; Ling-Yan He; Xiao-Feng Huang (Atmospheric Environment, 2024)

Multiomics Analyses Explore the Immunometabolic Interplay in the Liver of White Crucian Carp (Carassius cuvieri) After Aeromonas veronii Challenge - Fei Wang; Zi-Rou Zhong; Qing Xie; Jie Ou; Ning-Xia Xiong; Ming-Zhu Huang; Shi-Yun Li; Gang Hu; Zi-Le Qin; Sheng-Wei Luo (Marine Biotechnology, 2024)

Phylogenetic origin of an insect fauna at the boundary of the Palaearctic and Oriental realms: Evidence from ‘site‐based’ mitogenomics - Rui‐E Nie; Lu‐Lu Li; Anderson Feijó; Mei‐Xia Yang; Ming Bai; Thomas J. Creedy; Xu Jin; Jia‐Sheng Hao; Yong‐Ying Ruan; Hua‐Xi Liu; Beulah H. Garner; Ladislav Bocak; et al. (Journal of Biogeography, 2024)
Aim Knowledge of taxonomy and species distributions in highly diverse lineages of invertebrates remains too incomplete for the study of biogeographical patterns at the global scale. This limits the understanding of processes leading to the formation and maintenance of boundaries between major biogeographical realms. Site‐based metagenomic approaches may provide an alternative source of data for inference of historical processes of in situ speciation and interchange among biogeographical regions. We applied the methodology to explore the historical biogeography of the Qinling Mountains at the boundary of the Oriental and Palaearctic regions. Location The focal area in the Qinling Mountains; sites in Borneo, Panama, and Spain, representing the Oriental, Neotropical and Palaearctic faunas. Time Period Contemporary. Major Taxa Studied Chrysomelidae, a group of ~40,000 species with worldwide distribution. Methods Mass‐trapped insects were subjected to deep Illumina DNA sequencing and mitochondrial genome assembly, followed by phylogenetic analysis and historical biogeographical inference on a dated tree. The methodology produced 622 mitogenomes (304 newly sequenced) each representing a morphologically distinct species. Results Ancestral area reconstruction revealed that the Qinling fauna is a composite of distinct clades that, respectively, have Oriental or Palaearctic ancient origins, while in situ speciation and local clade formation were limited. The global diversity of Chrysomelidae consists of regionalised deep clades at the level of the major zoogeographic realms, which remain recognisable where these realms abut in the Qinling mountains. Yet, the Qinling fauna is clearly distinct from the source areas although local lineage ages are generally Main Conclusions The Qinling fauna is a composite of clades that have either Oriental or Palaearctic origin, indicating the important role of immigration at the realm boundary. Global site‐based phylogenetic analyses based on metagenomic sequencing can address previously intractable questions about the historical biogeography of poorly studied groups even without a fully developed taxonomy.

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

A combined IB-LB method for predicting the hydrodynamics of bionic undulating fin thrusters - Dan Xia; Ming Lei; Zhihan Li; Yunde Shi (Ocean Engineering, 2024)

Versatile MOF-based nanofibrous heterostructures for engineering the CO2 photoreduction activity and selectivity: From CO to C2H5OH - Xu-Chao Xia; Feng Cheng; Peng Sun; Amare Aregahegn Dubale; Hao Han; En-Tian Cui; Jun Song; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

A prospective cohort study of exposure to household pesticide with cardiovascular diseases mortality in older adults - Xiyao Zhao; Jiayuan Li; Yongqi Liu; Yunjie Liu; Xia Jiang; Lu Long; Jintao Wang; Yuqing Yao; Qin Zhang; Ming Li; Xiaomeng Li; Ben Zhang; et al. (Journal of Hazardous Materials, 2024)

Lotus pollen-derived nitrogen and phosphorus self-doped TiO2/carbon materials for photoelectrochemical application - Rui Chen; Ying-Ying Wang; Xia Jiang; Ming-Hao Ji; Ke-Xian Li; Hao-Yan Shi; Hai-Long Wang; Yan-Xin Chen; Can-Zhong Lu (Journal of Environmental Chemical Engineering, 2024)

Kidney-targeted antioxidant salvianolic acid B nanoparticles restoring lysosome homeostasis for acute kidney injury therapy - Jian-Li Chen; Xiao-Hui Jia; Xuan Wu; Ming-Heng Yuan; Xinyue Xia; Dan Yin; Xu Chen; Ze-Yun Gu; Jia-Zheng Liu; Li-Ping Bai; Kathy Qian Luo; Jianfang Wang; et al. (Chemical Engineering Journal, 2024)

Effects of High-Water Fluoride Exposure on IQ Levels in School-Age Children: A Cross-Sectional Study in Jiangsu, China - Yuting Xia; Yan Xu; Ming Shi; Song Liu; Suwan Liu; Hui Wang; Chaoyong Dai; Yunjie Ye; Mao Liu; Li Shang; Yang Wang; Peihua Wang (Exposure and Health, 2024)

Rapidly count crop seedling emergence based on waveform Method(WM) using drone imagery at the early stage - Jie Yuan; Xu Li; Meng Zhou; Hengbiao Zheng; Zhitao Liu; Yang Liu; Ming Wen; Tao Cheng; Weixing Cao; Yan Zhu; Xia Yao (Computers and Electronics in Agriculture, 2024)

Identification of SNPs and candidate genes associated with growth using GWAS and transcriptome analysis in Coilia nasus - Yue Yu; Shi-Ming Wan; Shuang-Meng Zhang; Jun-Qi Liu; Ai-Li Sun; Yao Wang; Yong-Fu Zhu; Shu-Xin Gu; Ze-Xia Gao (Aquaculture, 2024)

Weakened hydrological oscillation period increased the frequency of river algal blooms - Qiang HU; Yan CHEN; Rui XIA; Xiaoyu LIU; Ruining JIA; Kai ZHANG; Xiaoxuan LI; Chao YAN; Yao WANG; Yingze YIN; Xiang LI; Junde MING (Water Research, 2024)

Antihypertensive treatment during pregnancy induces long-term changes in gut microbiota and the behaviors of the attention deficit hyperactivity disorder offspring - Hong-Bao Li; Meng-Lu Xu; Wen-Jie Xia; Yuan-Yuan Dong; Bo Peng; Qing Su; Xiao-Min Wang; Jia-Yue Yu; Ya-Nan Gao; Jun-Zhe Wu; Meng-Yue Xu; Jin-Bao Yang; et al. (Toxicology and Applied Pharmacology, 2024)

The effect of artificial light at night (ALAN) on the characteristics of diapause of Aedes albopictus - Qing Liu; Heng-Duan Zhang; Dan Xing; Jing-Wen Xie; Yu-Tong Du; Ming Wang; Zi-Ge Yin; Nan Jia; Chun-Xiao Li; Teng Zhao; Yu-Ting Jiang; Yan-De Dong; et al. (Science of The Total Environment, 2024)

Integrated machine learning reveals aquatic biological integrity patterns in semi-arid watersheds - Lina Li; Rui Xia; Ming Dou; Kai Zhang; Yan Chen; Ruining Jia; Xiaoxuan Li; Jinghui Dou; Xiang Li; Qiang Hu; Hui Zhang; Nixi Zhong; et al. (Journal of Environmental Management, 2024)

Maintenance of callus-associated endophyte balance to mitigate oxidative browning in plant tissue culture practices - Yu-Tao Wang; Chun-Xiao Chen; Ping Zhou; Chun-Xi Lu; Yun Wen; Yu Li; Xiao-Xia Pan; Shu-Sheng Zhu; Ming-Zhi Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Identification, distribution, bactericidal and immunoregulatory activities of NK-lysins in grass carp (Ctenopharyngodon idella) - Gai Ling Wang; En Zhong Li; Da Hong Li; Ming Cheng Wang; Shan Shan Sun; Run Yan Xiong; Chuan Feng Li; Bao Jian Sun; Hai Xia Xie (Aquaculture, 2024)

Polar peripheral substituent-regulated organic/inorganic hybrid photocatalysts promoting the degradation of phenolic pollutants - Sheng-Hua Ma; Wei-Liang Jin; Hong-Xia Zhang; Shao-Cong Li; De-Ming Kong; Li-Na Zhu (Journal of Environmental Chemical Engineering, 2024)

Demethoxylation of curcumin enhances its inhibition on human and rat 17β-hydroxysteroid dehydrogenase 3: QSAR structure-activity relationship and in silico docking analysis - Zhongyao Ji; Jianmin Sang; Hong Wang; Miaomiao Xia; Ting Hao; Liping Chen; Han Lu; Shaowei Wang; Ming Yao; Linxi Li; Ren-shan Ge (Food and Chemical Toxicology, 2024)

KDM4B down-regulation facilitated breast cancer cell stemness via PHGDH upregulation in H3K36me3-dependent manner - Xin-Yu Wang; Hong-Ming Li; Ran Xia; Xiang Li; Xing Zhang; Tong-Zhao Jin; Hong-Sheng Zhang (Molecular and Cellular Biochemistry, 2024)

Environmental exposure to per- and polyfluoroalkyl substances mixture and asthma in adolescents - Yi-Fan Wang; Li Li; Xu Wang; Ya-Nan Yun; Xue-Lin Wang; En-Yang He; Ming-Kun Song; Xue-Hong Xia; Ying-Xue Zou (International Archives of Occupational and Environmental Health, 2024)

Elimination of methylmercury production potential in excessive sludge in wastewater treatment plants by sulfur addition - Shenyu OuYang; Yu Li; Ming Liu; Qingxia Zhao; Jinting Wang; Juntao Xia; Junfeng He; Feng Jiang (Science of The Total Environment, 2024)

Chiral separation and bioactivities of six pairs of enantiomeric dilignans from Magnolia officinalis var. biloba - Ying-Da Zang; Cai-xia Zang; Jin-Ying Tian; Kai-Ling Xu; Chuan Li; Chuang-Jun Li; Yang Yang; Fei Ye; Dan Zhang; Dong-Ming Zhang; Jie Ma (Phytochemistry, 2024)

Four uncommon cycloamphilectane-type diterpenoids with antibacterial activity from the South China Sea soft coral Sinularia brassica - Zi-Yi Xia; Man-Man Sun; Yang Jin; Ming-Zhi Su; Song-Wei Li; Hong Wang; Yue-Wei Guo (Phytochemistry, 2024)

CRISPR/Cas9-mediated ebony knockout causes melanin pigmentation and prevents moth Eclosion in Ectropis grisescens - Jia-Li Li; Shun-Si Li; Zi-Jun Luo; Ji Lu; Xiao-Ming Cai; Zong-Xiu Luo; Lei Bian; Chun-Li Xiu; Nan-Xia Fu; Nai-Yong Liu; Zhao-Qun Li (Pesticide Biochemistry and Physiology, 2024)

Multifunctional Eu3+-MOF for simultaneous quantification of malachite green and leuco-malachite green and efficient adsorption of malachite green - Yi-Fan Xia; Hou-Qun Yuan; Chen Qiao; Wei Li; Ran Wang; Peiyao Chen; Yan-Xia Li; Guang-Ming Bao (Journal of Hazardous Materials, 2024)

Ionic liquid microwave-assisted hydrodistillation extraction of Angelica sinensis essential oil and its own anti-inflammatory and antioxidant activities - Taotao Li; Huanxian Shi; Wenfei Wang; Jia Li; Tiantian Tang; Yujiao Wang; Ding Liu; Kai Yang; Xuan Wang; Jie Wang; Ning Xia; Jinhui Wang; et al. (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Effects of freeze–thaw actions on mechanical properties and constitutive model for diesel-contaminated soil - Xia Ye; Enlong Liu; Baofeng Di; Ming Li (European Journal of Environmental and Civil Engineering, 2024)

Covalently linked MOF@COF direct Z-scheme heterojunction for visible light-driven photocatalytic degradation of flotation agents - Hong-Xia Zhang; Sheng-Hua Ma; Hai-Xian Wang; Shao-Cong Li; Hai-Yun Shen; De-Ming Kong; Feng-Ying Wang; Li-Na Zhu (Journal of Environmental Chemical Engineering, 2024)

Contrasting Cu isotopes in mid-ocean ridge basalts and lower oceanic crust: Insights into the oceanic crustal magma plumbing systems - Zongqi Zou; Zaicong Wang; Yi-Gang Xu; Jakub Ciazela; Xia Wang; Stephen Foley; Wei-Qi Zhang; Wei Li; Ming Li; Yongsheng Liu (Earth and Planetary Science Letters, 2024)

VNS improves VSMC metabolism and arteriogenesis in infarcted hearts through m/n-AChR-Akt-SDF-1α in adult male rats - Xing-yuan Li; Jia-Qi Liu; Yan Wang; Yan Chen; Wen-hui Hu; Yan-xia Lv; Yan Wu; Jing Lv; Jun-ming Tang; Deying Kong (Journal of Molecular Histology, 2024)
Vagal nerve stimulation (VNS) provides a novel therapeutic strategy for injured hearts by activating cholinergic anti-inflammatory pathways. However, little information is available on the metabolic pattern and arteriogenesis of VSMCs after MI. VNS has been shown to stimulate the expression of CPT1α, CPT1β, Glut1, Glut4 and SDF-1α in coronary VSMCs, decreasing the number of CD68-positive macrophages while increasing CD206-positive macrophages in the infarcted hearts, leading to a decrease in TNF-α and IL-1β accompanied by a reduced ratio of CD68- and CD206-positive cells, which were dramatically abolished by atropine and mecamylamine in vivo. Knockdown of SDF-1α substantially abrogated the effect of VNS on macrophagecell alteration and inflammatory factors in infarcted hearts. Mechanistically, ACh induced SDF-1α expression in VSMCs in a dose-dependent manner. Conversely, atropine, mecamylamine, and a PI3K/Akt inhibitor completely eliminated the effect of ACh on SDF-1α expression. Functionally, VNS promoted arteriogenesis and improved left ventricular performance, which could be abolished by Ad-shSDF-1α. Thus, VNS altered the VSMC metabolism pattern and arteriogenesis to repair the infarcted heart by inducing SDF-1α expression, which was associated with the m/nAChR-Akt signaling pathway.

Dual-emissive Eu(III)-functionalized metal-organic frameworks for visual, rapid, and intelligent sensing of albendazole and albendazole sulfoxide in animal-origin food - Hou-Qun Yuan; Yi-Fan Xia; Yu-Fei Zhong; Wei Li; Hongda Zhu; Ran Wang; Peiyao Chen; Zhiming Gao; Xiangwei Zhu; Yan-Xia Li; Guang-Ming Bao (Analytica Chimica Acta, 2024)

Accumulation of livestock manure–derived heavy metals in the Hexi Corridor oasis agricultural alkaline soil and bioavailability to Chinese cabbage (Brassica pekinensis L.) after 4-year continuous application - Tian-Xia Guan; Zhao-Ping Lu; Ming Yue; Bao-Guo Li; Ai-Gen Fu; Xu-Dong Zhang; Zhong-Hu Li (Environmental Pollution, 2024)

Identification and fine-mapping of QYrAS286-2BL conferring adult-plant resistance to stripe rust in cultivated emmer wheat - Yuqin Li; Yanling Hu; Yun Jiang; Qiang Zhou; Yu He; Jingshu He; Xuejiao Chen; Xue Chen; Bo Jiang; Ming Hao; Shunzong Ning; Zhongwei Yuan; et al. (Theoretical and Applied Genetics, 2024)

Potentiation of the lateral habenula-ventral tegmental area pathway underlines the susceptibility to depression in mice with chronic pain - Chun-Kui Zhang; Pan Wang; Yuan-Yuan Ji; Jian-Shuai Zhao; Jun-Xiang Gu; Xian-Xia Yan; Hong-Wei Fan; Ming-Ming Zhang; Yu Qiao; Xiao-Die Liu; Bao-Juan Li; Ming-Hui Wang; et al. (Science China Life Sciences, 2024)

FTase inhibitors and cancer: prospects for use in targeted therapies - Ming-tao Xia; Ling Yu; Zhi-wei Yan; You-de Wang; Li-ying Zhang; Guang-xin Miao; Shuai Li (Medicinal Chemistry Research, 2024)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Paleoproterozoic crustal evolution of the Tarim Craton, NW China: Constraints from geochronology and geochemistry of orthogneisses and granitic veins in the Xingdi region of the Quruqtagh Block - Xiao-Hui Sun; Xiang Li; Ru-Xiong Lei; Matthew J. Brzozowski; Hua-Dong Ma; Wei Li; Li-Ming Xiong; Ming-Yi Xia; Chang-Zhi Wu (Precambrian Research, 2023)

Nonthermal plasma-activated polyvalent cerium-manganese bimetallic (hydro)oxide-functionalized nanographene for the removal of thallium(I) contaminants and mechanism exploration - Dongping Song; Tao Huang; Yinglan Luo; Di Wu; Shouze Li; Yujie Yan; Chaojun Yang; Qi Fang; Yuxing Wang; Yuxuan Feng; Nan Shang; Ming Xia; et al. (Journal of Cleaner Production, 2023)

Comprehensive analysis of combustion behaviors of hydrogen (H2)/diesel reactivity-controlled compression ignition (RCCI) in a light-duty diesel engine - Huiquan Duan; Ming Jia; Zhen Xu; Yaopeng Li; Guangqing Xia (Fuel, 2023)

Cinnamon essential oil based on NLRP3 inflammasome and renal uric acid transporters for hyperuricemia - Xuan Wang; Peijie Zhou; Huanxian Shi; Wenfei Wang; Taotao Li; Tiantian Tang; Jiawei Duan; Jinkai Li; Ning Xia; Jie Wang; Chao Chen; Jinhui Wang; et al. (Food Bioscience, 2023)

Efficient hybrid capacitive deionization with MnO2/g-C3N4 heterostructure: Enhancing Mn dz2 electron occupancy by interfacial electron bridge for fast charge transfer - Xueying Gao; Zhenzhen Fu; Yanfei Sun; Dewei Wang; Xiaoxuan Wang; Zishan Hou; Jinrui Wang; Xia Liu; Shiyu Wang; Shuyun Yao; Huiying Zhang; Shuyuan Li; et al. (Desalination, 2023)

Numerical investigation on self-propelled hydrodynamics of squid-like multiple tentacles with synergistic expansion - Zhihan Li; Dan Xia; Ming Lei; Han Yan (Ocean Engineering, 2023)

Carbon nano-onions acting as artificial pili enhance chloramphenicol degradation in an anaerobic membrane bioreactor - Ming-Chao Zhu; Yong-Ze Lu; Shou-Wen Chen; Zhao-Xia Hu; Jing-Wei Wang; Na Li; Raymond Jian-Xiong Zeng (Chemical Engineering Journal, 2023)

Tempo-spacial variation and source apportionment of atmospheric formaldehyde in the Pearl River Delta, China - Cheng-Bo Wei; Guang-He Yu; Li-Ming Cao; Heng-Xiao Han; Shi-Yong Xia; Xiao-Feng Huang (Atmospheric Environment, 2023)

A Novel Large-Scale Three-Dimensional Physical Model Experimental System for Deep Underground Engineering - Xia-Ting Feng; Zheng-Wei Li; Shi-Ming Mei; Jun Tian; Cheng-Xiang Yang; Zhi-Bin Yao; Ji-Kai Gao (Rock Mechanics and Rock Engineering, 2023)

Ångstrom-scale silver particles ameliorate collagen-induced and K/BxN-transfer arthritis in mice via the suppression of inflammation and osteoclastogenesis - Ze-Hui He; Jing-Tao Zou; Xia Chen; Jiang-Shan Gong; Ya Chen; Ling Jin; Yi-Wei Liu; Shan-Shan Rao; Hao Yin; Yi-Juan Tan; Zun Wang; Wei Du; et al. (Inflammation Research, 2023)

Whole-genome resequencing reveals genetic diversity and signatures of selection in mono-female grass carp (Ctenopharyngodon idella) - Dong-Yang Zhang; Xin-Ming Liu; Wei-Jie Huang; Yao Wang; Khan Anwarullah; Li-Fei Luo; Ze-Xia Gao (Aquaculture, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

The effect of stabilized culture of Lactobacillus rhamnosus GCC-3 on gut and liver health, and anti-viral immunity of zebrafish - Hui Liang; Yadong Xie; Ming Li; Jie Chen; Wenhao Zhou; Rui Xia; Qianwen Ding; Yuanyuan Yao; Zhen Zhang; Yalin Yang; Chao Ran; Zhigang Zhou (Fish & Shellfish Immunology, 2023)

Icariin inhibits hypertrophy by regulation of GPER1 and CaMKII/HDAC4/MEF2C signaling crosstalk in ovariectomized mice - Wenxia Zhao; Xiaoli Shan; Xueqin Li; Shuang Lu; Lei Xia; Huihua Chen; Chen Zhang; Wei Guo; Ming Xu; Rong Lu; Pei Zhao (Chemico-Biological Interactions, 2023)

Molecular characterization of stable QTL and putative candidate genes for grain zinc and iron concentrations in two related wheat populations - Mengjing Sun; Qiaoling Luo; Qi Zheng; Jingyang Tong; Yue Wang; Jie Song; Yelun Zhang; Zongjun Pu; Jianmin Zheng; Lianzheng Liu; Anding Zhou; Awais Rasheed; et al. (Theoretical and Applied Genetics, 2023)

Wuzi Yanzong Pill relieves MPTP-induced motor dysfunction and neuron loss by inhibiting NLRP3 inflammasome-mediated neuroinflammation - Tao Pan; Qi Xiao; Hui-Jie Fan; Lei Xu; Shao-Chen Qin; Li-Xia Yang; Xiao-ming Jin; Bao-Guo Xiao; Bo Zhang; Cun-Gen Ma; Zhi Chai (Metabolic Brain Disease, 2023)

Long-term detraining reverses the improvement of lifelong exercise on skeletal muscle ferroptosis and inflammation in aging rats: fiber-type dependence of the Keap1/Nrf2 pathway - Zhuang-Zhi Wang; Hai-Chen Xu; Huan-Xia Zhou; Chen-Kai Zhang; Bo-Ming Li; Jia-Han He; Pin-Shi Ni; Xiao-Ming Yu; Yun-Qing Liu; Fang-Hui Li (Biogerontology, 2023)

Seasonal variation characteristics of atmospheric peroxyacetyl nitrate (PAN) and its source apportionment in a megacity in southern China - Shi-Yong Xia; Xiao-Feng Huang; Zhi-Jie Li; Nan Fu; Zhen Jiang; Li-Ming Cao; Le-Wei Zeng; Guang-He Yu (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Surface engineering of Al2O3 nanotubes by ureasolysis method for activating persulfate degradation of antibiotics - Zheng-Wu Wang; Mei-Yun Xiao; Jun-Feng Tang; Ming-Qian Li; Xia-Yin Yin; Ting Wang; Yi-Zhou Zhu; Dai-Wen Pang; He-Fang Wang (Journal of Hazardous Materials, 2023)

Pilot-scale study on an advanced Fe-Cu process for refractory wastewater pretreatment - Jin-Hong Fan; Zhen-long Yao; De-li Wu; Xia Liu; Lu-ming Ma (Journal of Hazardous Materials, 2023)

Identification and application of species-specific peptide biomarkers from soft-shelled turtles (Pelodiscus sinensis) using post-translational modification detection-based peptidomics analysis - Haoran Xia; Xun Liu; Shuo Cai; Shengjun Chen; Song Li; Ming Zhao; Jin-ao Duan; Rui Liu; Shuying Han (Food Chemistry, 2023)

Codelivery of vorinostat and chloroquine by autophagy-inhibitory hollow ZrO2 nanoshells for synergistic combination chemotherapy - Jian-Li Chen; Xiao-Hui Jia; Xinyue Xia; Xuan Wu; Yan-Neng Xu; Gang Yuan; Ze-Yun Gu; Kathy Qian Luo; Ming-Heng Yuan; Ruibin Jiang; Jianfang Wang; Xiao-Ming Zhu (Chemical Engineering Journal, 2023)

Structural characteristics of the moss (bryophyte) layer and its underlying soil structure and water retention characteristics - Xia Hu; Zhou Gao; Xiao-Yan Li; Rui-Zhe Wang; Yuan-Ming Wang (Plant and Soil, 2023)

Non-monotonic Association Between Chlorinated Polyfluorinated Ether Sulfonic Acids Exposure and the Risk of Overweight/Obesity Status in Adults - Chu Chu; Qiu-Ling Fang; Xin-Xin Cui; Peng-Xin Dong; Zhengmin Qian; Stephen Edward McMillin; Steven W. Howard; Yan-Qiu Ou; Qing-Qing Li; Lu-Yin Wu; Li-Xia Liang; Shuang-Jian Qin; et al. (Exposure and Health, 2023)

Four organosulfur compounds from the seeds of Capsella bursa-pastoris and their anti-inflammatory activities - Zhen-Zhen Wei; Ti-Qiang Zhou; Zi-Ming Xia; Si-Fan Liu; Min Li; Guang-Jie Zhang; Ying Tian; Bin Li; Lin Wang (Natural Product Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Variations and driving mechanisms of desertification in the southeast section of the China-Mongolia-Russia Economic Zone - Yonghua Zhao; Shuyuan Yang; Li Liu; Xia Jia; Lei Han; Xuefeng Yuan; Ming Zhao; Peng Zhang (Science of The Total Environment, 2023)

Quantum computer-aided design for advanced superconducting qubit: Plasmonium - Feng-Ming Liu; Can Wang; Ming-Cheng Chen; He Chen; Shao-Wei Li; Zhong-Xia Shang; Chong Ying; Jian-Wen Wang; Yong-Heng Huo; Cheng-Zhi Peng; Xiaobo Zhu; Chao-Yang Lu; et al. (Science Bulletin, 2023)

Anti-apoptotic effect of adrenomedullin gene delivery on Leydig cells by suppressing TGF-β1 via the Hippo signaling pathway - You-wen Luo; Xia-lian Zhu; Ming-yong Li; Jian-hua Zhou; Zhi-min Yang; Tao Tong; Bing-hai Chen; Song-lin Qin; Bo-long Liu; Wei Hu (Reproductive Toxicology, 2023)

Overexpression of NADPH-cytochrome P450 reductase is associated with sulfoxaflor resistance and neonicotinoid cross-resistance in Nilaparvata lugens (Stål) - Minrong He; Xueyi Zhao; Xingyu Chen; Yiyan Shi; Shuai Wu; Fujin Xia; Rongyu Li; Ming Li; Hu Wan; Jianhong Li; Xun Liao (Pesticide Biochemistry and Physiology, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Structural classification of EZH2 inhibitors and prospects for the treatment of tumor: a review - Ling Yu; Ming-tao Xia; You-de Wang; Zhi-wei Yan; Li-ying Zhang; Shuai Li (Medicinal Chemistry Research, 2023)

Investigating the tourism image of mountain scenic spots in China through the lens of tourist perception - Feng-jiao Li; Xia Liao; Jia-ming Liu; Li-li Jiang; Meng-di Wang; Jin-feng Liu (Journal of Mountain Science, 2023)

Quantifying source effects based on rainwater δ18O from 10-year monitoring records in Southwest China - Yan-Xia Xue; Jian Zhang; Zhen Su; Yao Wu; Qi-sheng Liang; Ming-Qiang Liang; Xiang-Zhuo Liu; Chao-Jun Chen; Hai-Ying Qiu; Jun-Yun Li; Ting-Yong Li (Applied Geochemistry, 2023)

New insight into ZnO@ZIFs composite: an efficient photocatalyst with boosted light response ability and stability for CO2 reduction - Ran Zhao; Yahui Nie; Junyi Liu; Yuxi Wang; Ningbo Li; Qin Cheng; Ming Xia (Environmental Science and Pollution Research, 2023)

Crustal thickening and uplift of the northwestern Lhasa Terrane, central Tibetan Plateau: Insights from Mid-Eocene volcanic rocks in the Gerze Region - Xin-Hang Chai; Yun-Chuan Zeng; Ji-Feng Xu; Ming-Jian Li; Feng Huang; Xi-Jun Liu; Qin Chen; Hong-Xia Yu; Shu-Hui Ren (Lithos, 2023)

Effects of adsorption characteristics of carbocatalysts on persulfate-based advanced oxidation processes: Organic removal mechanisms and optimization strategies - Xiang-Feng Huang; Jing-Xi Yuan; Xia Zhao; Shuang-Qiang Li; Li-Heng Yang; Wen-Yan Li; Kai-Ming Peng; Chen Cai; Jia Liu (Chemical Engineering Journal, 2023)

PpIBH1-1 limits internode elongation of peach shoot in a dose-dependent manner - Mengmeng Zhang; Beibei Feng; Yun Chen; Mingxi Geng; Ming Li; Xianbo Zheng; Haipeng Zhang; Langlang Zhang; Bin Tan; Xia Ye; Wei Wang; Jidong Li; et al. (Plant Science, 2023)

The hybridization origin of the Chinese endemic herb genus Notopterygium (Apiaceae): Evidence from population genomics and ecological niche analysis - Yun Jia; Mi-Li Liu; Jordi López-Pujol; Rui-Wen Jia; Yi-Xuan Kou; Ming Yue; Tian-Xia Guan; Zhong-Hu Li (Molecular Phylogenetics and Evolution, 2023)

Exposure to cypermethrin pesticide disturbs the microbiome and disseminates antibiotic resistance genes in soil and the gut of Enchytraeus crypticus - Ming-Kang Jin; Qi Zhang; Yu-Tian Yang; Cai-Xia Zhao; Jian Li; Hongjie Li; Haifeng Qian; Dong Zhu; Yong-Guan Zhu (Journal of Hazardous Materials, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Identifying the airport as a key urban VOC source in the Pearl River Delta, China - Bo Zhu; Li-Ming Cao; Shi-Yong Xia; Ying-Bo Niu; Han-Yang Man; Ke Du; Kuangyou Yu; Xiao-Feng Huang (Atmospheric Environment, 2023)

Degradation and transformation of linear alkyl-benzene sulfonates (LAS) in integrated constructed wetland–microbial fuel cell systems - Huixin Wang; Xiaoou Wang; Meiyan Wang; Changping Zhang; Jiayin Li; Ming Xue; Weiyi Xia; Haijiao Xie (Chemosphere, 2023)

Preparation and characterization of carboxymethyl chitosan/pullulan composite film incorporated with eugenol and its application in the preservation of chilled meat - Zhen Zeng; Yu-Jing Yang; Qian Tu; Yu-Ying Jian; Da-Ming Xie; Ting Bai; Shan-Shan Li; Yun-Tao Liu; Cheng Li; Cai-Xia Wang; Ai-Ping Liu (Meat Science, 2023)

Lignin-based covalent organic polymers with improved crystallinity for non-targeted analysis of chemical hazards in food samples - Zhan-Chao Li; Wei Li; Rui Wang; Dong-Xia Wang; An-Na Tang; Xiao-Peng Wang; Xiao-Ping Gao; Gai-Ming Zhao; De-Ming Kong (Journal of Hazardous Materials, 2023)

In-situ growth of carbon nanotubes for improving the performance of Co-N/C catalysts in proton exchange membrane fuel cell - Xi-Ming Qu; Shu-Hu Yin; Ya-Ni Yan; Jian Yang; Yan-Rong Li; Xiao-Yang Cheng; Fa Lu; Chong-Tai Wang; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2023)

Obstructive sleep apnea-increased DEC1 regulates systemic inflammation and oxidative stress that promotes development of pulmonary arterial hypertension - Xiaoming Li; Xiang Zhang; Xiaozhi Hou; Xin Bing; Fangyuan Zhu; Xinhao Wu; Na Guo; Hui Zhao; Fenglei Xu; Ming Xia (Apoptosis, 2023)

Experimental evaluation of a hybrid solar dryer with flexible open sorption thermal energy storage unit on demand for burdock root drying - Rong Zhu; Qiongfen Yu; Ming Li; Yiping Xia; Aimin Li; Danya Zhan; Yinning Li; Yunfeng Wang (Environmental Science and Pollution Research, 2023)

Oyster (Crassostrea gigas) ferritin should be a promising Fe2+ nanocarrier - Han Li; Xiaoyu Xia; Zhenyu Wang; Jiachen Zang; Ming Du (Food Chemistry, 2023)

Analysis of PAT1 subfamily members in the GRAS family of upland cotton and functional characterization of GhSCL13-2A in Verticillium dahliae resistance - Chen Chen; Li-Li Lu; Shu-Ya Ma; Yan-Peng Zhao; Na Wu; Wen-Jie Li; Li Ma; Xian-Hui Kong; Zong-Ming Xie; Yu-Xia Hou (Plant Cell Reports, 2023)

Treatment and remediation of metal-contaminated water and groundwater in mining areas by biological sulfidogenic processes: A review - Yu Li; Qingxia Zhao; Ming Liu; Jiahua Guo; Juntao Xia; Jinting Wang; Yanying Qiu; Jiahui Zou; Weiting He; Feng Jiang (Journal of Hazardous Materials, 2023)

Control of low-temperature polyoxymethylene dimethyl ethers (PODEn)/gasoline combustion considering fuel concentration, fuel reactivity, and intake temperature at low loads - Huiquan Duan; Ming Jia; Hui Wang; Yaopeng Li; Guangqing Xia (Fuel, 2023)

Absence of water content contrast between lithosphere and asthenosphere in subduction zone - Yuto Sato; Eiichi Takahashi; Chang-Ming Xing; Li Li; Ze-Xian Cui; Wan-Feng Zhang; Xiao-Ping Xia (Earth and Planetary Science Letters, 2023)

Assessing the difference of biochar and aged biochar to improve soil fertility and cabbage (Brassica oleracea var. capitata) productivity - Hao Xia; Muhammad Riaz; Cong Ming; Yuxuan Li; Xiangling Wang; Cuncang Jiang (Journal of Soils and Sediments, 2023)

Large-scale mariculture of the sponge Haliclona simulans on floating rafts in Zhao'an Bay, Fujian Province, China - Zhunfei Li; Guangyuan Xia; Huilong Ou; Ming Chen; Yingzhe You; Jun Chen (Aquaculture, 2023)

Marked shifts of harmful algal blooms in the Bohai Sea linked with combined impacts of environmental changes - Xiao-Yu Li; Ren-Cheng Yu; Anthony J. Richardson; Chaojiao Sun; Ruth Eriksen; Fan-Zhou Kong; Zheng-Xi Zhou; Hui-Xia Geng; Qing-Chun Zhang; Ming-Jiang Zhou (Harmful Algae, 2023)

A hybrid kinetics integrating feed-consumption rate and product selectivity models for Fischer-Tropsch synthesis over an industrial cobalt-based catalyst - Congcong Niu; Shupeng Guo; Ming Xia; Jungang Wang; Litao Jia; Bo Hou; Baojun Wang; Debao Li (Chemical Engineering Journal, 2023)

Coupled carbon structure and iron species for multiple periodate-based oxidation reaction - Ling Xiang; Eydhah Almatrafi; Hailan Yang; Haoyang Ye; Fanzhi Qin; Huan Yi; Yukui Fu; Xiuqin Huo; Wu Xia; Hong Li; Ming Yan; Chengyun Zhou; et al. (Chemical Engineering Journal, 2023)

Genistein attenuates neuroinflammation and oxidative stress and improves cognitive impairment in a rat model of sepsis-associated encephalopathy: potential role of the Nrf2 signaling pathway - Buyun Shi; Ming Chen; Zhi Xia; Wen Tang; Yong Li; Chenguang Qin; Amir Ahmadi; Chengjiao Huang; Hui Xu (Metabolic Brain Disease, 2023)

Retraction Note: Knockdown of long non‑coding RNA TUG1 depresses apoptosis of hippocampal neurons in Alzheimer’s disease by elevating microRNA‑15a and repressing ROCK1 expression - Xia Li; Sheng‑Wu Wang; Xi‑Ling LI; Feng‑Yuan Yu; Hai‑Ming Cong (Inflammation Research, 2023)

Water-in-zircon: a discriminant between S- and I-type granitoid - Jing Mo; Xiao-Ping Xia; Peng-Fei Li; Christopher J. Spencer; Chun-Kit Lai; Jian Xu; Qing Yang; Ming-Dao Sun; Yang Yu; Luke Milan (Contributions to Mineralogy and Petrology, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Genome-Wide Identification Reveals the Potential Functions of the bZIP Gene Family in Common Bean (Phaseolus vulgaris) in Response to Salt Stress During the Sprouting Stage - Qi Zhang; Wen-jing Zhang; Zhen-gong Yin; Wei-jia Li; Chun-Yang Xia; Hao-Yue Sun; Yi-Ming Yang; Hong-Bin Wu; Shuo Zhang; Hao-hao Zhao; Wen-Hui Zhang; Yong-xia Guo; et al. (Journal of Plant Growth Regulation, 2022)

Role of carnitine in adaptation of Chromohalobacter salexigens DSM 3043 and its mutants to osmotic and temperature stress in defined medium - Xiang-Lin Meng; Xia Gao; Yuan-Ming Si; Li-Li Xu; Li-Zhong Guo; Wei-Dong Lu (Extremophiles, 2022)

Molecular characterization of a novel victorivirus isolated from Botryosphaeria dothidea, the causal agent of longan leaf spot disease - Jiali Li; Lifeng Zhai; Meixin Zhang; Gangjun Luo; Yongqi Wen; Tingting Cao; Huan Xia; Jiayu Zhang; Ming Liu (Archives of Virology, 2022)

The impact of coastal upwelling on coral reef ecosystem under anthropogenic influence: Coral reef community and its response to environmental factors - Wentao Zhu; Yuxiao Ren; Xiangbo Liu; Duanjie Huang; Jingquan Xia; Ming Zhu; Hongyang Yin; Rouwen Chen; Xiubao Li (Frontiers in Marine Science, 2022)
Mass coral bleaching is a severe threat to coral reefs in the era of global warming, and upwelling areas may serve as thermal refugia for coral reefs by mitigating the effects of heating anomalies. This study seeks to examine the impact of the Qiongdong upwelling (QDU) on the coastal coral reefs of the Hainan Island. The environmental variables (i.e., physiochemical parameters, coastal land use) differed significantly in upwelling and non-upwelling areas. In particular, the presence of colder and more saline water was the important indicator of coastal upwelling. In the QDU, turf algae and macroalgae dominated the algae communities, but habitat-specific environment and coastal development contributed to lower calcified algae, coral larvae replenishment and live corals cover. Lower abundance of coral reefs fishes could be attributed to the disappearance of live corals, increase of algae coverage, low habitat complexity and strong wave exposure at upwelling stations. Upwelling-related environmental parameters, wave exposure, land use and potential local stressors were revealed as major driving factors related to significant spatial changes in stony coral and fish communities. Overall, the present findings suggest that the Qiongdong upwelling has the potential to provide thermal refuge for coral reefs, but is severely affected by local anthropogenic activities.

Advancements of nature nanocage protein: preparation, identification and multiple applications of ferritins - Han Li; Xiaoyu Xia; Xiaoyi Tan; Jiachen Zang; Zhenyu Wang; Hesham R. EI-Seedi; Ming Du (Critical Reviews in Food Science and Nutrition, 2022)

Intestinal Models for Personalized Medicine: from Conventional Models to Microfluidic Primary Intestine-on-a-chip - Xiang-Guang Li; Ming-xia Chen; Su-qing Zhao; Xiu-qi Wang (Stem Cell Reviews and Reports, 2022)

Modification effects of seasonal and temperature variation on the association between exposure to nitrogen dioxide and ischemic stroke onset in Shenzhen, China - Yuchen Tian; Ming Xiang; Ji Peng; Yanran Duan; Ying Wen; Suli Huang; Lei Li; Shuyuan Yu; Jinquan Cheng; Xia Zhang; Peng Wang (International Journal of Biometeorology, 2022)

Comparison between the exotic Coreopsis grandiflora and native Dendranthema indicum across variable nitrogen deposition conditions - Li-Jun Xing; Ming-Yan Li; Si-Yu Jiang; Wei Li; Shao-Xia Guo; Hai-Mei Li; Xiao Guo (Acta Physiologiae Plantarum, 2022)

The fate of flavonoids after oral administration: a comprehensive overview of its bioavailability - Abid Naeem; Yang Ming; Hu Pengyi; Kang Yong Jie; Liu Yali; Zhang Haiyan; Xiao Shuai; Li Wenjing; Wu Ling; Zhang Ming Xia; Liu Shan Shan; Zheng Qin (Critical Reviews in Food Science and Nutrition, 2022)

RIG-I acts as a tumor suppressor in melanoma via regulating the activation of the MKK/p38MAPK signaling pathway - Rui Guo; Shun-Yuan Lu; Jin-Xia Ma; Qian-Lan Wang; Lu Zhang; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; Hong-Xin Zhang (Human Cell, 2022)
Studies have indicated that RIG-I may act as a tumor suppressor and participate in the tumorigenesis of some malignant diseases. However, RIG-I induces distinct cellular responses via different downstream signaling pathways depending on the cell type. To investigate the biological function and underlying molecular mechanism of RIG-I in the tumorigenesis of melanoma, we constructed RIG-I knockout, RIG-I -overexpressing B16-F10 and RIG-I knockdown A375 melanoma cell lines, and analyzed the RIG-I-mediated change in the biological behavior of tumor cells in spontaneous and poly (I:C)-induced RIG-I activation. Cell proliferation, cell cycling, apoptosis and migration were detected by CCK-8 assay, BrdU incorporation assay, Annexin V–PI staining assay and Transwell assay, respectively. In vivo tumorigenicity was evaluated by tumor xenograft growth in nude mice and subsequently by Ki67 staining and TUNEL assays. Furthermore, Western blotting was utilized to explore the underlying mechanism of RIG-I in melanoma cells. Our data showed that RIG-I promotes apoptosis and inhibits proliferation by G1 phase cell cycle arrest in the melanoma cell lines. Mechanistically, RIG-I induced the phosphorylation of p38 MAPK and MAPK kinases MKK3 and MKK4. In conclusion, the current study demonstrated that RIG-I suppressed the development of melanoma by regulating the activity of the MKK/p38 MAPK signaling pathway, which is relevant to research on novel therapeutic targets for this malignant disease.

Otolith Marking With Strontium for Stock Assessment in Coilia nasus - Ming-Zhi Liu; Ri-jin Jiang; Hui Zhang; Fan Yang; Xia-Fang Li; Guang-Peng Feng; Rui Yin; Feng Chen (Frontiers in Marine Science, 2022)
Mass stock enhancement and release are excellent ways to recover Coilia nasus resources. However, it is challenging to evaluate stock enhancement effectively, and it is important to establish a method suitable for estimating C. nasus populations. We explored the effectiveness of marking otoliths in these fish with strontium by immersing C. nasus in hexahydrate strontium chloride solutions. We used laser ablation inductively coupled plasma mass spectrometry to measure the strontium content of otoliths and fish bodies. The larvae (40 d post hatch) were reared in five different concentrations of strontium (0, 12, 24, 48, and 60 mg/L) for 7 d, followed by treatment in non-additive water for 3 wk. The results showed that the cumulative mortality rate was not significantly different between treatment and control groups ( P >0.05), except in the group treated with 24 mg/L strontium. The swimming and feeding behaviors did not change significantly, indicating that strontium did not negatively affect survival in this species. The strontium/calcium ratios of otoliths in the control group were stable (1.78–2.32 mmol/mol), whereas those of the experimental (marked) groups ranged widely (4.47–61.02 mmol/mol). The strontium/calcium ratios increased with increasing strontium concentration, but gradually returned to baseline values, resulting in a 100% success rate of marking with strontium. Following immersion in 12 mg/L strontium, strontium levels in the body returned to normal after 24 d. In summary, a treatment of 12 mg/L strontium for 4 d was identified as viable for marking. We confirmed the feasibility of strontium marking for the mass marking and release of C. nasus . This marking method does not affect the physiology of the fish and may provide a new approach for reasonable and scientific stock assessment of C. nasus post hatch.

Qipengyuania thermophila sp. nov., isolated from a Chinese hot spring - Zi-Yu Zhao; Ting-Ting Xia; Jian-Yu Jiao; Lan Liu; Qing-Yang Su; Meng-Meng Li; Ai-Ping Lv; Yu-Ting Ouyang; Wen-Jun Li; Hong Ming (Archives of Microbiology, 2022)

Characteristics of the TDRD1 gene promoter in chickens - Xiaomin Gao; Xiaolin Sun; Pei Xu; Xiang Shi; Ming Zhang; Xia Yuan; Jingyi Jiang; Kai Jin; Qisheng Zuo; Yani Zhang; Bichun Li (Molecular Genetics and Genomics, 2022)

ALKBH5 promotes the progression of infantile hemangioma through regulating the NEAT1/miR-378b/FOSL1 axis - Kun Peng; Ren-Peng Xia; Fan Zhao; Yong Xiao; Ti-Dong Ma; Ming Li; Yong Feng; Chong-Gao Zhou (Molecular and Cellular Biochemistry, 2022)

Spatiotemporal evolution of chlorophyll-a concentration from MODIS data inversion in the middle and lower reaches of the Hanjiang River, China - Zhuo Chen; Ming Dou; Rui Xia; Guiqiu Li; Lisha Shen (Environmental Science and Pollution Research, 2022)

Identifying critical failure factors of green supply chain management in China’s SMEs with a hierarchical cause–effect model - Shuo Gao; Ming Kim Lim; Renlu Qiao; Chensi Shen; Chentao Li; Li Xia (Environment, Development and Sustainability, 2022)

A new isoflavone from the fruits of Ficus auriculata and its antibacterial activity - Tai-Ming Shao; Hai-Xia Liao; Xiao-Bao Li; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2022)

Williamsia soli sp. nov., an actinobacterium isolated from soil at a thermal power plant in Yantai, China - Ming-Jing Zhang; Xue-Han Li; Li-Yang Peng; Shuai-Ting Yun; Zhuo-Cheng Liu; Yan-Xia Zhou (Archives of Microbiology, 2022)

Ferroptosis inhibitory constituents from the fruits of Cullen corylifolium - Aftab Yaseen; Fan Yang; Xia Zhang; Fu Li; Bin Chen; Ahmed Hassan Ibrahim Faraag; Ming-Kui Wang; Xiao-Fei Shen; Lun Wang (Natural Product Research, 2021)

Muricauda chongwuensis sp. nov., isolated from coastal seawater of China - Ming-Xia Chen; Xiao-Yu He; He-Yang Li (Archives of Microbiology, 2021)

Terpenoids with neurotrophic and anti-neuroinflammatory activities from the cultures of the fungus Cyathus stercoreus - Xia Yin; Jianzhao Qi; Yixiao Li; Ze’an Bao; Peng Du; Rongwei Kou; Weiwei Wang; Jin-Ming Gao (Natural Product Research, 2021)

Inhibition of Maternal c-Src Ameliorates the Male Offspring Hypertension by Suppressing Inflammation and Neurotransmitters in the Paraventricular Nucleus - Qing Su; Xiao-Jing Yu; Qing Yang; Xiao-Min Wang; Wen-Jie Xia; Hong-Bao Li; Kai-Li Liu; Qiu-Yue Yi; Yu-Ming Kang (Cardiovascular Toxicology, 2021)

Application of Plant Print Identification Technology in Salt-resistant Soybean Breeding - Yan Li; Xia Li; Zi-qi Chen; Ying Ma; Guang-yu Yang; Ying Zhang; Ming-chun Sun; Li-hong Zhang; Jin-meng Chu; Jing-mei Lu; Jun Zhu; Ji-hong You (Journal of Plant Growth Regulation, 2021)

DREAM - Zhu-Qing Gong; Peng Gao; Chao Jiang; Xiu-Xia Xing; Hao-Ming Dong; Tonya White; F. Xavier Castellanos; Hai-Fang Li; Xi-Nian Zuo (Neuroinformatics, 2021)
Rhythms of the brain are generated by neural oscillations across multiple frequencies. These oscillations can be decomposed into distinct frequency intervals associated with specific physiological processes. In practice, the number and ranges of decodable frequency intervals are determined by sampling parameters, often ignored by researchers. To improve the situation, we report on an open toolbox with a graphical user interface for decoding rhythms of the brain system (DREAM). We provide worked examples of DREAM to investigate frequency-specific performance of both neural (spontaneous brain activity) and neurobehavioral (in-scanner head motion) oscillations. DREAM decoded the head motion oscillations and uncovered that younger children moved their heads more than older children across all five frequency intervals whereas boys moved more than girls in the age of 7 to 9 years. It is interesting that the higher frequency bands contain more head movements, and showed stronger age-motion associations but weaker sex-motion interactions. Using data from the Human Connectome Project, DREAM mapped the amplitude of these neural oscillations into multiple frequency bands and evaluated their test-retest reliability. The resting-state brain ranks its spontaneous oscillation’s amplitudes spatially from high in ventral-temporal areas to low in ventral-occipital areas when the frequency band increased from low to high, while those in part of parietal and ventral frontal regions are reversed. The higher frequency bands exhibited more reliable amplitude measurements, implying more inter-individual variability of the amplitudes for the higher frequency bands. In summary, DREAM adds a reliable and valid tool to mapping human brain function from a multiple-frequency window into brain waves.

Altered structural and functional connectivity in CSF1R-related leukoencephalopathy - Fei-Xia Zhan; Ze-Yu Zhu; Qing Liu; Hai-Yan Zhou; Xing-Hua Luan; Xiao-Jun Huang; Xiao-Li Liu; Wo-Tu Tian; Shi-Ge Wang; Xiao-Xuan Song; Guang Chen; Ming-Liang Zhao; et al. (Brain Imaging and Behavior, 2021)

Study on Microwave Heating Order and Electromagnetic Characteristics of Copper and Gold Ores - Feng Lin; Xia-Ting Feng; Gao-Ming Lu; Xiang-Xin Su; Shi-Ping Li; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2021)

Subcellular Localization of the D27 Protein in Sugarcane (Saccharum spp. Hybrids) Using an Optimized Protoplast Isolation, Purification, and Transient Gene Expression Protocol - Zhuan-di Wu; Xin Hu; Feng-gang Zan; Yong-bao Pan; David M. Burner; Zheng-ying Luo; Jia-yong Liu; Li-ping Zhao; Li Yao; Yong Zhao; Xin-long Liu; Hong-ming Xia; et al. (Sugar Tech, 2021)

TLR8 in the Trigeminal Ganglion Contributes to the Maintenance of Trigeminal Neuropathic Pain in Mice - Lin-Xia Zhao; Ming Jiang; Xue-Qiang Bai; De-Li Cao; Xiao-Bo Wu; Jing Zhang; Jian-Shuang Guo; Tong-Tong Chen; Juan Wang; Hao Wu; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)
Trigeminal neuropathic pain (TNP) is a significant health problem but the involved mechanism has not been completely elucidated. Toll-like receptors (TLRs) have recently been demonstrated to be expressed in the dorsal root ganglion and involved in chronic pain. Here, we show that TLR8 was persistently increased in the trigeminal ganglion (TG) neurons in model of TNP induced by partial infraorbital nerve ligation (pIONL). In addition, deletion or knockdown of Tlr8 in the TG attenuated pIONL-induced mechanical allodynia, reduced the activation of ERK and p38-MAPK, and decreased the expression of pro-inflammatory cytokines in the TG. Furthermore, intra-TG injection of the TLR8 agonist VTX-2337 induced pain hypersensitivity. VTX-2337 also increased the intracellular Ca 2+ concentration, induced the activation of ERK and p38, and increased the expression of pro-inflammatory cytokines in the TG. These data indicate that TLR8 contributes to the maintenance of TNP through increasing MAPK-mediated neuroinflammation. Targeting TLR8 signaling may be effective for the treatment of TNP.

Effects of hydrological change on the risk of riverine algal blooms: case study in the mid-downstream of the Han River in China - Lisha Shen; Ming Dou; Rui Xia; Guiqiu Li; Baiheng Yang (Environmental Science and Pollution Research, 2021)

Changes in soil available cadmium and bacterial communities after fallowing depend on contamination levels - Xinqi Wang; Xia Lu; Xingyun Yi; Zhuoqing Li; Yimin Zhou; Guilan Duan; Ming Lei (Journal of Soils and Sediments, 2021)

Mechanism of a catastrophic landslide occurred on May 12, 2019, Qinghai Province, China - Min Xia; Guang Ming Ren; Xi Li Yang (Landslides, 2021)

Surface Temperature Changes Projected by FGOALS Models under Low Warming Scenarios in CMIP5 and CMIP6 - Shang-Min Long; Kai-Ming Hu; Gen Li; Gang Huang; Xia Qu (Advances in Atmospheric Sciences, 2021)

Reduced magnitude and shifted seasonality of CO 2 sink by experimental warming in a coastal wetland - Baoyu Sun; Liming Yan; Ming Jiang; Xinge Li; Guangxuan Han; Jianyang Xia (Ecology, 2021)
Coastal wetlands have the highest carbon sequestration rate per unit area among all unmanaged natural ecosystems. However, how the magnitude and seasonality of the CO 2 sink in coastal wetlands will respond to future climate warming remains unclear. Here, based on measurements of ecosystem CO 2 fluxes in a field experiment in the Yellow River Delta, we found that experimental warming (i.e., a 2.4°C increase in soil temperature) reduced net ecosystem productivity (NEP) by 23.7% across two growing seasons of 2017–2018. Such a reduction in NEP resulted from the greater decrease in gross primary productivity (GPP) than ecosystem respiration (ER) under warming. The negative warming effect on NEP mainly occurred in summer (−43.9%) but not in autumn (+61.3%), leading to a shifted NEP seasonality under warming. Further analyses showed that the warming effects on ecosystem CO 2 exchange were mainly controlled by soil salinity and its corresponding impacts on species composition. For example, warming increased soil salinity (+35.0%), reduced total aboveground biomass (−9.9%), and benefited the growth of plant species with high salt tolerance and late peak growth. To the best of our knowledge, this study provides the first experimental evidence on the reduced magnitude and shifted seasonality of CO 2 exchange under climate warming in coastal wetlands. These findings underscore the high vulnerability of wetland CO 2 sink in coastal regions under future climate change.

Localization and characterization of Citrus centromeres by combining half-tetrad analysis and CenH3-associated sequence profiling - Qiang-Ming Xia; Lu-Ke Miao; Kai-Dong Xie; Zhao-Ping Yin; Xiao-Meng Wu; Chun-Li Chen; Jude W. Grosser; Wen-Wu Guo (Plant Cell Reports, 2020)

Iron Aggravates the Depressive Phenotype of Stressed Mice by Compromising the Glymphatic System - Shanshan Liang; Yan Lu; Zexiong Li; Shuai Li; Beina Chen; Manman Zhang; Binjie Chen; Ming Ji; Wenliang Gong; Maosheng Xia; Alexei Verkhratsky; Xu Wu; et al. (Neuroscience Bulletin, 2020)

Grafting Alleviates Cadmium Toxicity and Reduces Its Absorption by Tomato - Yongdong Xie; Huaqiang Tan; Guochao Sun; Huanxiu Li; Dong Liang; Hui Xia; Xun Wang; Ming’an Liao; Honghong Deng; Jin Wang; Yi Tang (Journal of Soil Science and Plant Nutrition, 2020)

Sulfide ore prospecting in carbon-containing stratum using comprehensive time-domain induced polarization and controlled-source audio-frequency magnetotellurics - Ren-Bin Sun; Li-Xia Chu; Gui-Bin Zhang; Qiu-Ming Cheng; Yun-Chuan Xiang; Bin Hu; Chang-Rong Zhang; Jian-Fu Li; Yi-Jun Zhao (Applied Geophysics, 2020)

Effects of the Lower Airway Secretions on Airway Opening Pressures and Suction Pressures in Critically Ill COVID-19 Patients: A Computational Simulation - Zhenglong Chen; Ming Zhong; Li Jiang; Nanshan Chen; Shengjin Tu; Yuan Wei; Ling Sang; Xia Zheng; Chunyuan Zhang; Jiale Tao; Linhong Deng; Yuanlin Song (Annals of Biomedical Engineering, 2020)

Effects of intercropping accumulator plants and applying their straw on the growth and cadmium accumulation of Brassica chinensis L. - Yi Tang; Liming Wang; Yongdong Xie; Xuena Yu; LiJin Lin; Huanxiu Li; Ming’an Liao; Zhihui Wang; Guochao Sun; Dong Liang; Hui Xia; Xun Wang; et al. (Environmental Science and Pollution Research, 2020)

RETRACTED ARTICLE: Knockdown of long non-coding RNA TUG1 depresses apoptosis of hippocampal neurons in Alzheimer’s disease by elevating microRNA-15a and repressing ROCK1 expression - Xia Li; Sheng-Wu Wang; Xi-Ling LI; Feng-Yuan Yu; Hai-Ming Cong (Inflammation Research, 2020)

Future trends and guidance for the triple bottom line and sustainability: a data driven bibliometric analysis - Ming-Lang Tseng; Chia-Hao Chang; Chun-Wei Remen Lin; Kuo-Jui Wu; Qing Chen; Li Xia; Bing Xue (Environmental Science and Pollution Research, 2020)
This study conducts a comprehensive literature review of articles on the triple bottom line (TBL) published from January 1997 to September 2018 to provide significant insights and support to guide further discussion. There were three booms in TBL publications, occurring in 2003, 2011, and 2015, and many articles attempt to address the issue of sustainability by employing the TBL. This literature analysis includes 720, 132, and 58 articles from the Web of Science (WOS), Inspec, and Scopus databases, respectively, and reveals the gaps in existing research. To discover the barriers and points of overlap, these articles are categorized into six aspects of the TBL: economic, environmental, social, operations, technology, and engineering. Examining the top 3 journals in terms of published articles on each aspect reveals the research trends and gaps. The findings provide solid evidence confirming the argument that the TBL as currently defined is insufficient to cover the entire concept of sustainability. The social and engineering aspects still require more discussion to support the linkage of the TBL and to reinforce its theoretical basis. Additionally, to discover the gaps in the data sources, theories applied, methods adopted, and types of contributions, this article summarizes 82 highly cited articles covering each aspect. This article offers theoretical insights by identifying the top contributing countries, institutions, authors, keyword networks, and authorship networks to encourage scholars to push the current discussion further forward, and it provides practical insights to bridge the gap between theory and practice for enhancing the efficiency and effectiveness of improvements.

Well hydraulics of temporally varying artificial recharge with well clogging in confined aquifers - Jiong Li; Jin-Jian Chen; Ming-Guang Li; Xiao-He Xia (Arabian Journal of Geosciences, 2020)

Development and validation of high-throughput and low-cost STARP assays for genes underpinning economically important traits in wheat - Yuying Wu; Ming Li; Zhonghu He; Susanne Dreisigacker; Weie Wen; Hui Jin; Shengnan Zhai; Faji Li; Fengmei Gao; Jindong Liu; Rongge Wang; Pingzhi Zhang; et al. (Theoretical and Applied Genetics, 2020)

A novel plant protein-disulfide isomerase participates in resistance response against the TYLCV in tomato - Tong Li; Ya-Hui Wang; Ying Huang; Jie-Xia Liu; Guo-Ming Xing; Sheng Sun; Sen Li; Zhi-Sheng Xu; Ai-Sheng Xiong (Planta, 2020)

Naphthalene exerts non-target effects on the abundance of active fungi by stimulating basidiomycete abundance - Li-ying Lan; Li Zhang; Ya Shen; Jian Zhang; Wan-qin Yang; Zhen-feng Xu; Yang Liu; Shu-qin He; Wei Zhou; Han Li; Li-xia Wang; Si-ning Liu; et al. (Journal of Mountain Science, 2020)

The trichome-specific acetolactate synthase NtALS1 gene, is involved in acylsugar biosynthesis in tobacco (Nicotiana tabacum L.) - Ai-Xia Chang; Biao Chen; Ai-Guo Yang; Ri-Sheng Hu; Quan-Fu Feng; Ming Chen; Xiao-Ning Yang; Cheng-Gang Luo; Yang-Yang Li; Yuan-Ying Wang (Planta, 2020)

Selenium accumulation characteristics of Cyphomandra betacea (Solanum betaceum) seedlings - Linjin Lin; Jing Sun; Tonghao Cui; Xiong Zhou; Ming’an Liao; Yunmin Huan; Liu Yang; Caifang Wu; Xianmin Xia; Yuxi Wang; Zhiyu Li; Jinpeng Zhu; et al. (Physiology and Molecular Biology of Plants, 2020)

Antifungal, anti-inflamatory and neuritogenic activity of newly-isolated compounds from Disporopsis aspersa - Fang-Li Gang; Feng Zhu; Chao-Fu Yang; Xiao-Ting Li; Hua Yang; Ming-Xia Sun; Wen-Jun Wu; Ji-Wen Zhang (Natural Product Research, 2020)

Haploidentical hematopoietic cell transplantation for severe acquired aplastic anemia: a case-control study of post-transplant cyclophosphamide included regimen vs. anti-thymocyte globulin & colony-stimulating factor-based regimen - Lanping Xu; Bin Fu; Wenjing Wang; Yajing Xu; Depei Wu; Shunqing Wang; Qifa Liu; Linghui Xia; Sujun Gao; Ming Jiang; Jianmin Wang; Xi Zhang; et al. (Science China Life Sciences, 2020)

The BIG gene controls size of shoot apical meristems in Arabidopsis thaliana - Wen Jie Zhang; Li Ming Zhai; Hai Xia Yu; Jing Peng; Shan Shan Wang; Xian Sheng Zhang; Ying Hua Su; Li Ping Tang (Plant Cell Reports, 2020)

Effects of carboxymethyl chitosan on the growth and nutrient uptake in Prunus davidiana seedlings - Dandi Xu; Hongyan Li; Lijin Lin; Ming’an Liao; Qunxian Deng; Jin Wang; Xiulan Lv; Honghong Deng; Dong Liang; Hui Xia (Physiology and Molecular Biology of Plants, 2020)

ABNORMAL FLOWER AND GRAIN 1 encodes OsMADS6 and determines palea identity and affects rice grain yield and quality - Xiaoqi Yu; Saisai Xia; Qiankun Xu; Yuanjiang Cui; Ming Gong; Dali Zeng; Qiang Zhang; Lan Shen; Guiai Jiao; Zhenyu Gao; Jiang Hu; Guangheng Zhang; et al. (Science China Life Sciences, 2020)

The regulatory cascades of antibiotic production in Streptomyces - Haiyang Xia; Xinqiao Zhan; Xu-Ming Mao; Yong-Quan Li (World Journal of Microbiology and Biotechnology, 2020)

Major advances in studies of the physical geography and living environment of China during the past 70 years and future prospects - Fahu Chen; Bojie Fu; Jun Xia; Duo Wu; Shaohong Wu; Yili Zhang; Hang Sun; Yu Liu; Xiaomin Fang; Boqiang Qin; Xin Li; Tingjun Zhang; et al. (Science China Earth Sciences, 2019)

Effects of mutual grafting on cadmium accumulation characteristics of first post-generations of Bidens pilosa L. and Galinsoga parviflora Cav. - Hongyan Li; Jin Wang; Lijin Lin; Ming’an Liao; Xiulan Lv; Yi Tang; Xun Wang; Hui Xia; Dong Liang; Wei Ren; Wei Jiang (Environmental Science and Pollution Research, 2019)

Effects of self-rooted grafting on growth and cadmium accumulation in post-grafting generations of soybean (Glycine max) - Jin Wang; Huan Yao; Lijin Lin; Yi Tang; Dong Liang; Hui Xia; Xiulan Lv; Ming’an Liao; Guochao Sun; Huanxiu Li; Xun Wang; Wei Ren (Environmental Monitoring and Assessment, 2019)

The Microwave-Induced Fracturing of Hard Rock - Gao-Ming Lu; Xia-Ting Feng; Yuan-Hui Li; Xiwei Zhang (Rock Mechanics and Rock Engineering, 2019)

Chemical constituents from Ginkgo biloba L. male flowers and their biological activities - Min Li; Zi-ming Xia; Bin Li; Ying Tian; Guang-jie Zhang; Chen Xu; Jun-xing Dong (Medicinal Chemistry Research, 2019)

Solidification/stabilization of municipal solid waste incineration fly ash using uncalcined coal gangue–based alkali-activated cementitious materials - Shujie Zhao; Faheem Muhammad; Lin Yu; Ming Xia; Xiao Huang; Binquan Jiao; Ning Lu; Dongwei Li (Environmental Science and Pollution Research, 2019)

Population structure and genetic diversity of Vibrio parahaemolyticus from a coastal area of China based on a multi-locus sequence typing (MLST) scheme - Yu Li; Hong-Qiu Yin; Jun Xia; Hong Luo; Ming-Yi Wang (Antonie van Leeuwenhoek, 2019)

Experimental Investigation on the Effects of Microwave Treatment on Basalt Heating, Mechanical Strength, and Fragmentation - Gao-Ming Lu; Xia-Ting Feng; Yuan-Hui Li; Ferri Hassani; Xiwei Zhang (Rock Mechanics and Rock Engineering, 2019)

Complex rock slope deformation at Laxiwa Hydropower Station, China: background, characterization, and mechanism - Min Xia; Guang Ming Ren; Tian Bin Li; Ming Cai; Tian Jun Yang; Zong Li Wan (Bulletin of Engineering Geology and the Environment, 2019)

Identification of duplicated Cited3 genes and their responses to hypoxic stress in blunt snout bream (Megalobrama amblycephala) - Hong-Hong Guo; Yuan Sun; Xue-li Zhang; Xia-Yun Jiang; Shu-Ming Zou (Fish Physiology and Biochemistry, 2019)

Astaxanthin enhances hematology, antioxidant and immunological parameters, immune-related gene expression, and disease resistance against in Channa argus - Mu-Yang Li; Xin-Yu Liu; Chang-Ge Xia; Gui-Qin Wang; Dong-Ming Zhang (Aquaculture International, 2019)

Mechanism underlying 2n male and female gamete formation in lemon via cytological and molecular marker analysis - Kai-Dong Xie; Qiang-Ming Xia; Jun Peng; Xiao-Meng Wu; Zong-Zhou Xie; Chun-Li Chen; Wen-Wu Guo (Plant Biotechnology Reports, 2019)

Experimental Study and Estimation of Groundwater Fluctuation and Ground Settlement due to Dewatering in a Coastal Shallow Confined Aquifer - Jiong Li; Ming-Guang Li; Lu-Lu Zhang; Hui Chen; Xiao-He Xia; Jin-Jian Chen (Journal of Marine Science and Engineering, 2019)
The coastal micro-confined aquifer (MCA) in Shanghai is characterized by shallow burial depth, high artesian head, and discontinuous distribution. It has a significant influence on underground space development, especially where the MCA is directly connected with deep confined aquifers. In this paper, a series of pumping well tests were conducted in the MCA located in such area to investigate the dewatering-induced groundwater fluctuations and stratum deformation. In addition, a numerical method is proposed for the estimation of hydraulic parameter, and an empirical prediction method is developed for dewatering-induced ground settlement. Test results show that groundwater drawdowns and soil settlement can be observed not only in MCA but also in the aquifers underneath it. This indicates that there is a close hydraulic connection among each aquifer. Moreover, the distributions and development of soil settlement at various depths are parallel to those of groundwater drawdowns in most areas of the test site except the vicinity of pumping wells, where collapse-induced subsidence due to high-speed flow may occur. Furthermore, the largest deformation usually occurs at the top of the pumping aquifer instead of the ground surface, because the top layer is expanded due to the stress arch formed in it. Finally, the proposed methods are validated to be feasible according to the pumping well test results and can be employed to investigate the responses of groundwater fluctuations and stratum deformations due to dewatering in MCA.

Chronic Intracerebroventricular Infusion of Metformin Inhibits Salt-Sensitive Hypertension via Attenuation of Oxidative Stress and Neurohormonal Excitation in Rat Paraventricular Nucleus - Xiao-Jing Yu; Ya-Nan Zhao; Yi-Kang Hou; Hong-Bao Li; Wen-Jie Xia; Hong-Li Gao; Kai-Li Liu; Qing Su; Hui-Yu Yang; Bin Liang; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

A new polyketide purpurogenic acid: the activated production of polyketides by the diethyl sulphate mutagenesis of marine-derived Penicillium purpurogenum G59 - Ming-Wen Xia; Yu Yang; Rui Xu; Chang-Wei Li; Cheng-Bin Cui (Natural Product Research, 2019)

A new cyclohexenone from the tin mine tailings-derived fungus Aspergillus flavus YIM DT 10012 - Wei-Xun Chunyu; Jiang-Yuan Zhao; Zhang-Gui Ding; Xiu-Lin Han; Yong-Xia Wang; Jian-Hai Ding; Fei Wang; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2019)

Application Research on Gob-Side Entry Retaining Methods in No. 1200 Working Face in Zhongxing Mine - Sun Xiao-ming; Li Gan; Song Peng; Miao Chengyu; Zhao Chengwei; Li Qi; Xia Xing (Geotechnical and Geological Engineering, 2019)

An invasive population of Solidago canadensis is less sensitive to warming and nitrogen-addition than its native population in an invaded range - Yang Peng; Jian-Xia Yang; Xiao-Hui Zhou; Pei-Hao Peng; Jing-Ji Li; Shu-Min Zhang; Wei-Ming He (Biological Invasions, 2019)

β2-AR regulates the expression of AKR1B1 in human pancreatic cancer cells and promotes their proliferation via the ERK1/2 pathway - Ming-Bing Xiao; Dan-Dan Jin; Yu-Jie Jiao; Wen-Kai Ni; Jin-Xia Liu; Li-Shuai Qu; Cui-Hua Lu; Run-Zhou Ni; Feng Jiang; Wei-Chang Chen (Molecular Biology Reports, 2018)

Cadmium-accumulator straw application alleviates cadmium stress of lettuce (Lactuca sativa) by promoting photosynthetic activity and antioxidative enzyme activities - Yi Tang; Yongdong Xie; Guochao Sun; Huaqiang Tan; Lijin Lin; Huanxiu Li; Ming’an Liao; Zhihui Wang; Xiulan Lv; Dong Liang; Hui Xia; Xun Wang; et al. (Environmental Science and Pollution Research, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

Arbuscular mycorrhizal fungi enhance antioxidant defense in the leaves and the retention of heavy metals in the roots of maize - Fangdong Zhan; Bo Li; Ming Jiang; Xianrong Yue; Yongmei He; Yunsheng Xia; Youshan Wang (Environmental Science and Pollution Research, 2018)

Transcriptome analysis of differentially expressed genes in rabbits’ ovaries by digital gene-expression profiling - Tao Huang; Ya-dong Wang; Ming-ming Xue; Xue Feng; Cai-Xia Sun; An-si Wang; Shu-yu Xie; Meng Zhang; Gui-Rong Sun; Ming Li (Genes & Genomics, 2018)

Tissue Distribution and Gender-Specific Protein Expression of Cytochrome P450 in five Mouse Genotypes with a Background of FVB - Jiamei M. Chen; Qisong S. Zhang; Xiaoyan Y. Li; Xia Gong; Yanjiao J. Ruan; Sijing J. Zeng; Linlin L. Lu; Xiaoxiao X. Qi; Ying Wang; Ming Hu; Lijun J. Zhu; Zhongqiu Q. Liu (Pharmaceutical Research, 2018)

SOX2-mediated inhibition of miR-223 contributes to STIM1 activation in phenylephrine-induced hypertrophic cardiomyocytes - Zhi-Hong Zhao; Jun Luo; Hai-xia Li; Sai-hua Wang; Xin-ming Li (Molecular and Cellular Biochemistry, 2018)

Ecological risk assessment of the Gannan Plateau, northeastern Tibetan Plateau - Dong-xia Yue; Jian-jun Zeng; Chao Yang; Ming-liang Zou; Kai Li; Guan-guang Chen; Jian-jun Guo; Xiao-feng Xu; Xing-min Meng (Journal of Mountain Science, 2018)

Both widespread PEP‐CTERM proteins and exopolysaccharides are required for floc formation of Zoogloea resiniphila and other activated sludge bacteria - Na Gao; Ming Xia; Jingcheng Dai; Dianzhen Yu; Weixing An; Shuyang Li; Shuangyuan Liu; Penghui He; Liping Zhang; Zhenbin Wu; Xuezhi Bi; Shouwen Chen; et al. (Environmental Microbiology, 2018)
Summary Bacterial floc formation plays a central role in the activated sludge (AS) process, which has been widely utilized for sewage and wastewater treatment. The formation of AS flocs has long been known to require exopolysaccharide biosynthesis. This study demonstrates an additional requirement for a PEP‐CTERM protein in Zoogloea resiniphila , a dominant AS bacterium harboring a large exopolysaccharide biosynthesis gene cluster. Two members of a wide‐spread family of high copy number‐per‐genome PEP‐CTERM genes, transcriptionally regulated by the RpoN sigma factor and accessory PrsK‐PrsR two‐component system and at least one of these, pepA , must be expressed for Zoogloea to build the floc structures that allow gravitational sludge settling and recycling. Without PrsK or PrsR, Zoogloea cells were planktonic rather than flocculated and secreted exopolysaccharides were released into the growth broth in soluble form. Overexpression of PepA could circumvent the requirement of rpoN , prsK and prsR for the floc‐forming phenotype by fixing the exopolysaccharides to bacterial cells. However, overexpression of PepA, which underwent post‐translational modifications, could not rescue the long‐rod morphology of the rpoN mutant. Consistently, PEP‐CTERM genes and exopolysaccharide biosynthesis gene cluster are present in the genome of the floc‐forming Nitrospira comammox and Mitsuaria strain as well as many other AS bacteria.

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Effects of melatonin on the growth and cadmium characteristics of Cyphomandra betacea seedlings - Lijin Lin; Jianhua Li; Fabo Chen; Ming’an Liao; Yi Tang; Dong Liang; Hui Xia; Yunsong Lai; Xun Wang; Cheng Chen; Wei Ren (Environmental Monitoring and Assessment, 2018)

Characterization of a Putative S-layer Protein of a Colonial Microcystis Strain - Wei-Wei Li; Ming-Sheng Xia; Wen-Bin Li; Li-Wen Liu; Ying Yang; Jian-Hong Li (Current Microbiology, 2018)

Integrated in silico–in vitro screening of ovarian cancer peroxisome proliferator-activated receptor-γ agonists against a biogenic compound library - Gui-Lian Zhang; Feng-Ying Liu; Jing Zhang; Li-Ping Wang; Er-Xia Jia; Shi-Ming Lv (Medicinal Chemistry Research, 2018)

Removal of NO with the hexamminecobalt solution catalyzed by the carbon treated with oxalic acid - Xiang-li Long; Hai-xia Cao; Bei-bei Duan; Ming-lei Jia (Environmental Science and Pollution Research, 2017)

Effects of mutual intercropping on the cadmium accumulation in accumulator plants Stellaria media, Malachium aquaticum, and Galium aparine - Qiyu Lu; Jianhua Li; Fabo Chen; Ming’an Liao; Lijin Lin; Yi Tang; Dong Liang; Hui Xia; Yunsong Lai; Xun Wang; Cheng Chen; Wei Ren (Environmental Monitoring and Assessment, 2017)

A novel missense mutation of $$ADAR1$$ ADAR 1 gene in a Chinese family leading to dyschromatosis symmetrica hereditaria and literature review - Shuai-Mei Liu; Meng-Xia Ni; Ming-Chao Zhang; Pei-Ran Zhu; Qiu-Yu Wu; Wei-Jun Jiang; Jing Zhang; Wei-Wei Li; Xin-Yi Xia (Journal of Genetics, 2017)

Identification of a novel reassortant A (H9N6) virus in live poultry markets in Poyang Lake region, China - Heng Zhang; Mingbin Liu; Xiaoxu Zeng; Xiang Zhao; Zhiqiang Deng; Lei Yang; Wenbing Chen; Zi Li; Ming Jiao; Wen Xia; Bin Han; Haiying Chen; et al. (Archives of Virology, 2017)

Transcriptomic insights into the alternative splicing‐mediated adaptation of the entomopathogenic fungus Beauveria bassiana to host niches: autophagy‐related gene 8 as an example - Wei‐Xia Dong; Jin‐Li Ding; Yang Gao; Yue‐Jin Peng; Ming‐Guang Feng; Sheng‐Hua Ying (Environmental Microbiology, 2017)
Summary Alternative splicing (AS) regulates various biological processes in fungi by extending the cellular proteome. However, comprehensive studies investigating AS in entomopathogenic fungi are lacking. Based on transcriptome data obtained via dual RNA‐seq, the first overview of AS events was developed for Beauveria bassiana growing in an insect haemocoel. The AS was demonstrated for 556 of 8840 expressed genes, accounting for 5.4% of the total genes in B. bassiana . Intron retention was the most abundant type of AS, accounting for 87.1% of all splicing events and exon skipping events were rare, only accounting for 2.0% of all events. Functional distribution analysis indicated an association between alternatively spliced genes and several physiological processes. Notably, B. bassiana autophagy‐related gene 8 ( BbATG8 ), an indispensable gene for autophagy, was spliced at an alternative 5′ splice site to generate two transcripts ( BbATG8‐α and BbATG8‐β ). The BbATG8‐α transcript was necessary for fungal autophagy and oxidation tolerance, while the BbATG8‐β transcript was not. These two transcripts differentially contributed to the formation of conidia or blastospores as well as fungal virulence. Thus, AS acts as a powerful post‐transcriptional regulatory strategy in insect mycopathogens and significantly mediates fungal transcriptional adaption to host niches.

Hyperaccumulator straw improves the cadmium phytoextraction efficiency of emergent plant Nasturtium officinale - Keqiang Li; Lijin Lin; Jin Wang; Hui Xia; Dong Liang; Xun Wang; Ming’an Liao; Li Wang; Li Liu; Cheng Chen; Yi Tang (Environmental Monitoring and Assessment, 2017)

Two new diketopiperazines from the tin mine tailings-derived fungus Schizophyllum commune YIM DT 10058 - Wei-Xun Chunyu; Zhang-Gui Ding; Jiang-Yuan Zhao; Yong-Xia Wang; Xiu-Lin Han; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2017)

Analysis of global gene expression profiles during the flowering initiation process of Lilium × formolongi - Yu-Fan Li; Ming-Fang Zhang; Meng Zhang; Gui-Xia Jia (Plant Molecular Biology, 2017)

As contamination alters rhizosphere microbial community composition with soil type dependency during the rice growing season - Chang-Ming Li; Chen-Xia Lei; Yu-Ting Liang; Chang-Qing Chen; Bo Sun (Paddy and Water Environment, 2017)

Metabolomics Analysis Reveals the Salt-Tolerant Mechanism in Glycine soja - Dong-shuang Yang; Jing Zhang; Ming-xia Li; Lian-xuan Shi (Journal of Plant Growth Regulation, 2017)

The alternative splicing of EAM8 contributes to early flowering and short-season adaptation in a landrace barley from the Qinghai-Tibetan Plateau - Tengfei Xia; Lianquan Zhang; Jinqing Xu; Lei Wang; Baolong Liu; Ming Hao; Xi Chang; Tangwei Zhang; Shiming Li; Huaigang Zhang; Dengcai Liu; Yuhu Shen (Theoretical and Applied Genetics, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Cloning and expression analysis of zygote arrest 1 (Zar1) in New Zealand white rabbits - DAN WANG; SHU-YU XIE; WEI ZHANG; CAI-XIA SUN; TAO HUANG; AN-SI WANG; XUE-LEI HAN; GUI-RONG SUN; MING LI (Journal of Genetics, 2017)

NFAT5 protects astrocytes against oxygen–glucose–serum deprivation/restoration damage via the SIRT1/Nrf2 pathway - Xun Xia; Bo Qu; Yun-Ming Li; Li-Bin Yang; Ke-Xia Fan; Hui Zheng; Hai-Dong Huang; Jian-Wen Gu; Yong-Qin Kuang; Yuan Ma (Journal of Molecular Neuroscience, 2017)

Three new species of Boletaceae from the Heishiding Nature Reserve in Guangdong Province, China - Fang Li; Kuan Zhao; Qing-Li Deng; Ming Zhang; Christian Staehelin; Xiao-Xia Chen; Hong-Ying Chen; Geng-Shen Wang; Bing-Sheng Li (Mycological Progress, 2016)

High-performance size-exclusion chromatography studies on the formation and distribution of polar compounds in camellia seed oil during heating - Hong-xia Feng; Rokayya Sam; Lian-zhou Jiang; Yang Li; Wen-ming Cao (Journal of Zhejiang University-SCIENCE B, 2016)

Seasonal dynamics of Botryosphaeria dothidea infections and symptom development on apple fruits and shoots in China - Xu Zhao; Gao-lei Zhang; Bao-hua Li; Xiang-ming Xu; Xiang-li Dong; Cai-xia Wang; Gui-fang Li (European Journal of Plant Pathology, 2016)

Assessment of biostimulation and bioaugmentation for removing chlorinated volatile organic compounds from groundwater at a former manufacture plant - Shu Zhang; Zhen Hou; Xiao-ming Du; Dong-ming Li; Xiao-xia Lu (Biodegradation, 2016)

Truncated type IV pilin PilA108 activates the intramembrane protease AlgW to cleave MucA and PilA108 itself in vitro - Ronghui Li; Ryan T. Withers; Jingcheng Dai; Jing Ruan; Wei Li; Yujun Dai; Weixing An; Dianzhen Yu; Hehong Wei; Ming Xia; Chunyuan Tian; Hongwei D. Yu; et al. (Archives of Microbiology, 2016)

Distinct effect of pH on N uptake and assimilation in two conifer species - Sen Meng; Chun-xia Zhang; Li Su; Yi-Ming Li; Yang Cao; Zhong Zhao (Trees, 2016)

Impact of Heat Shock Protein A 12B Overexpression on Spinal Astrocyte Survival Against Oxygen-Glucose-Serum Deprivation/Restoration in Primary Cultured Astrocytes - Xun Xia; Yuan Ma; Li-bin Yang; Jing-ming Cheng; Tao Yang; Ke-xia Fan; Yun-ming Li; En-yu Liu; Lin Cheng; Hai-dong Huang; Jian-wen Gu; Yong-qin Kuang (Journal of Molecular Neuroscience, 2016)

Economical Succinic Acid Production from Sugarcane Juice by Actinobacillus succinogenes Supplemented with Corn Steep Liquor and Peanut Meal as Nitrogen Sources - Nai-kun Shen; Si-ming Liao; Qing-yan Wang; Yan Qin; Qi-xia Zhu; Jing Zhu; Yi Li; Ri-bo Huang (Sugar Tech, 2016)

OsMSR15 encoding a rice C2H2-type zinc finger protein confers enhanced drought tolerance in transgenic Arabidopsis - Xin Zhang; Bin Zhang; Ming Juan Li; Xu Ming Yin; Li Fang Huang; Yan Chun Cui; Man Ling Wang; Xinjie Xia (Journal of Plant Biology, 2016)

Inhibition effects of high calcium concentration on anaerobic biological treatment of MSW leachate - Yi Xia; Pin-Jing He; Hong-Xia Pu; Fan Lü; Li-Ming Shao; Hua Zhang (Environmental Science and Pollution Research, 2016)

The pseudorabies virus DNA polymerase processivity factor UL42 exists as a monomer in vitro and in vivo - Yi-Ping Wang; Li-Ping Huang; Wen-Juan Du; Yan-Wu Wei; De-Li Xia; Hong-Li Wu; Li Feng; Chang-Ming Liu (Archives of Virology, 2016)

The effects of abscisic acid (ABA) addition on cadmium accumulation of two ecotypes of Solanum photeinocarpum - Jin Wang; Lijin Lin; Li Luo; Ming’an Liao; Xiulan Lv; Zhihui Wang; Dong Liang; Hui Xia; Xun Wang; Yunsong Lai; Yi Tang (Environmental Monitoring and Assessment, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Deficient and excess dietary selenium levels affect growth performance, blood cells apoptosis and liver HSP70 expression in juvenile yellow catfish Pelteobagrus fulvidraco - Jun-Ru Hu; Yan-Hua Huang; Guo-Xia Wang; Ying-Xia Wu; Jian-An Xian; An-Li Wang; Jun-Ming Cao (Fish Physiology and Biochemistry, 2016)

Expression of Shewanella frigidimarina fatty acid metabolic genes in E. coli by CRISPR/cas9-coupled lambda Red recombineering - Jun Xia; Ling Wang; Jian-bo Zhu; Cheng-jun Sun; Ming-gang Zheng; Li Zheng; Ying-hua Lou; Lei Shi (Biotechnology Letters, 2016)

Deghosting towed streamer data in τ/p domain based on rough sea surface reflectivity - Xing-Yan Zhang; Dong-Ming Pan; Wen-Ying Shi; Zhong-Yu Fang; Zhi-Wei Dan; Li-Xia Zhang (Applied Geophysics, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Development of a test strip for rapid detection of lactoperoxidase in raw milk - Hong-xia Che; Bo Tian; Li-na Bai; Li-ming Cheng; Li-li Liu; Xiao-na Zhang; Zhan-mei Jiang; Xiao-xi Xu (Journal of Zhejiang University-SCIENCE B, 2015)

Potential dental pulp revascularization and odonto-/osteogenic capacity of a novel transplant combined with dental pulp stem cells and platelet-rich fibrin - Yong-Jin Chen; Yin-Hua Zhao; Ya-Juan Zhao; Nan-Xia Liu; Xin Lv; Qiang Li; Fa-Ming Chen; Min Zhang (Cell and Tissue Research, 2015)

Spiculisporic acid analogues of the marine-derived fungus, Aspergillus candidus strain HDf2, and their antibacterial activity - Rong Wang; Zhi Kai Guo; Xiang Min Li; Fu Xiao Chen; Xia Fei Zhan; Ming Hui Shen (Antonie van Leeuwenhoek, 2015)

Growth of embryo and gene expression of nutrient transporters in the small intestine of the domestic pigeon (Columba livia) - Ming-xia Chen; Xiang-guang Li; Jun-xian Yang; Chun-qi Gao; Bin Wang; Xiu-qi Wang; Hui-chao Yan (Journal of Zhejiang University-SCIENCE B, 2015)

Systemic nematicidal activity and biocontrol efficacy of Bacillus firmus against the root-knot nematode Meloidogyne incognita - Jing Xiong; Qiaoni Zhou; Haiyan Luo; Liqiu Xia; Lin Li; Ming Sun; Ziquan Yu (World Journal of Microbiology and Biotechnology, 2015)

Preparation and Characterization of a Novel Extracellular Polysaccharide with Antioxidant Activity, from the Mangrove-Associated Fungus Fusarium oxysporum - Yan-Li Chen; Wen-Jun Mao; Hong-Wen Tao; Wei-Ming Zhu; Meng-Xia Yan; Xue Liu; Tian-Tian Guo; Tao Guo (Marine Biotechnology, 2015)

Effects of intermediate metabolite carboxylic acids of TCA cycle on Microcystis with overproduction of phycocyanin - Shijie Bai; Jingcheng Dai; Ming Xia; Jing Ruan; Hehong Wei; Dianzhen Yu; Ronghui Li; Hongmei Jing; Chunyuan Tian; Lirong Song; Dongru Qiu (Environmental Science and Pollution Research, 2015)

A method to label biological molecules with dsDNA coated gold nanoparticles - Ming Xing; Fangliang Li; Yingshan Dong; Zhenxiang Yu; Xia Chen (Biotechnology Letters, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

OsCML4 improves drought tolerance through scavenging of reactive oxygen species in rice - Xu Ming Yin; Li Fanng Huang; Xin Zhang; Man Ling Wang; Guo Yun Xu; Xin Jie Xia (Journal of Plant Biology, 2015)

Design and synthesis of N-hydroxytriazole-4-carboxamides as HIV integrase inhibitors - Yue-Xia Bai; Long-Ji Li; Xiao-Li Wang; Cheng-Chu Zeng; Li-Ming Hu (Medicinal Chemistry Research, 2015)

Construction of corneal epithelium with human amniotic epithelial cells and repair of limbal deficiency in rabbit models - Qing Zhou; Xiao-Yong Liu; Yu-Xia Ruan; Li Wang; Ming-Ming Jiang; Jing Wu; Jian Chen (Human Cell, 2015)

The Effects of Wubeizi Ointment on the Proliferation of Keloid-Derived Fibroblasts - Ji-cun Ding; Zhi-ming Tang; Xiao-xiang Zhai; Xiang-hui Chen; Jing-guo Li; Cui-xia Zhang (Cell Biochemistry and Biophysics, 2015)
To evaluate the effectiveness of the Wubeizi (WBZ) ointment on keloid-derived fibroblasts. The primary cells of the keloid-derived fibroblasts were cultured and the effectiveness of the WBZ ointment at different concentrations was examined by MTT colorimetric methods on keloid-derived fibroblasts. The WBZ ointment showed inhibitory effects on proliferating the keloid-derived fibroblasts ( P < 0.01)in a time- and dose-dependent manner. The proportion of cells in S stage was significantly higher in each of the WBZ ointment group than in the control group ( P <0.01), and the proportion of G 2 + M stage cells was significantly lower than that of control group, which was statistically significant ( P < 0.01).The inhibitory effects of the S and G 2 + M stage increased with higher drug concentrations ( P < 0.05). Conclusion: The WBZ ointment can inhibit the proliferation of the keloid-derived fibroblasts in a time- and dose- dependent manner.

Increased prevalence of hepatitis C virus subtype 6a in China: a comparison between 2004–2007 and 2008–2011 - Xia Rong; Ru Xu; Huaping Xiong; Min Wang; Ke Huang; Qiuyu Chen; Chengyao Li; Qiao Liao; Jieting Huang; Wenjie Xia; Guangping Luo; Xin Ye; et al. (Archives of Virology, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

The expression profile and promoter analysis of β-N-acetylglucosaminidases in the silkworm Bombyx mori - Yuan-fen Zhai; Ming-xia Huang; Yu Wu; Guo-dong Zhao; Jie Du; Bing Li; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2014)

Plasmid-encoding vasostatin inhibited the growth and metastasis of human hepatocellular carcinoma cells - Xing-chen Peng; Ming Wang; Xu-xia Chen; Jing Liu; Gui-hua Xiao; Hong-li Liao (Molecular and Cellular Biochemistry, 2014)

Identification and genetic characterization of avian-origin H3N2 canine influenza viruses isolated from the Liaoning province of China in 2012 - Xinyan Yang; Chunguo Liu; Fei Liu; Dafei Liu; Yan Chen; Haifeng Zhang; Liandong Qu; Yijing Li; Donghua Xia; Ming Liu (Virus Genes, 2014)

Halomonas qiaohouensis sp. nov., isolated from salt mine soil in southwest China - Yong-Xia Wang; Wei Xiao; Ming-Hua Dong; Qin Zhao; Zhi-Ying Li; Yong-Hong Lai; Xiao-Long Cui (Antonie van Leeuwenhoek, 2014)

Geochronology of magmatism and mineralization of the Daheishan giant porphyry molybdenum deposit, Jilin Province, Northeast China: constraints on ore genesis and implications for geodynamic setting - Ling-Li Zhou; Qing-Dong Zeng; Jian-Ming Liu; Henrik Friis; Zuo-Lun Zhang; Xiao-Xia Duan; Ting-Guang Lan (International Geology Review, 2014)

Control of autophagy maturation by acid sphingomyelinase in mouse coronary arterial smooth muscle cells: protective role in atherosclerosis - Xiang Li; Ming Xu; Ashley L. Pitzer; Min Xia; Krishna M. Boini; Pin-Lan Li; Yang Zhang (Journal of Molecular Medicine, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Biological control of Ralstonia wilt, Phytophthora blight, Meloidogyne root-knot on bell pepper by the combination of Bacillus subtilis AR12, Bacillus subtilis SM21 and Chryseobacterium sp. R89 - Hong-Xia Liu; Shi-Mo Li; Yu-Ming Luo; Lai-Xin Luo; Jian-Qiang Li; Jian-Hua Guo (European Journal of Plant Pathology, 2014)

Haemocyte Apoptosis of the Tiger Shrimp Penaeus monodon Exposed to Cadmium - Jian-An Xian; Bin Li; Hui Guo; Yu-Tao Miao; Jian-Min Ye; Li-Na Feng; Chao-Xia Ye; Xun-Bin Pan; An-Li Wang; Xuan-Ming Hao (Bulletin of Environmental Contamination and Toxicology, 2014)

A tripeptide (NSK) inhibits Japanese encephalitis virus infection in vitro and in vivo - Chen Li; Ling-ling Ge; Ya-ling Yu; Li Huang; Yue Wang; Ming-xia Sun; Hassan Ishag; Liang-xiao Ma; Xue-hua Li; Zhi-qiang Shen; Xiang Mao (Archives of Virology, 2014)

The metabolism of 8-heptadecene in Pyropia (Bangiaceae, Rhodophyta) - Min Zhang; Rui-Xia Li; Chuan-Ming Hu; Li-En Yang; Jun Tang; Qin-Qin Lu; Tao Zhang; Zong-Gen Shen; Song-Dong Shen; Pu Xu; Jian-Yi Zhu (Journal of Applied Phycology, 2014)

Inhibition of 12/15 lipoxygenase by baicalein reduces myocardial ischemia/reperfusion injury via modulation of multiple signaling pathways - Lina Song; Hui Yang; Hong-Xia Wang; Cui Tian; Yu Liu; Xiang-Jun Zeng; Erhe Gao; Yu-Ming Kang; Jie Du; Hui-Hua Li (Apoptosis, 2014)

Expression analysis and RNA interference of BmCarE-10 gene from Bombyx mori - Guo-dong Zhao; Ming-xia Huang; Yi-ling Zhang; Xue-cen Wang; Jie Du; Bing Li; Yu-hua Chen; Ya-xiang Xu; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2014)

Family-based association study of ZNF533, DOCK4 and IMMP2L gene polymorphisms linked to autism in a northeastern Chinese Han population - Shuang Liang; Xue-lai Wang; Ming-yang Zou; Han Wang; Xue Zhou; Cai-hong Sun; Wei Xia; Li-jie Wu; Takashi X. Fujisawa; Akemi Tomoda (Journal of Zhejiang University-SCIENCE B, 2014)

Genetic diversity analysis of yams (Dioscorea spp.) cultivated in China using ISSR and SRAP markers - Zhi Gang Wu; Xiao Xia Li; Xin Chun Lin; Wu Jiang; Zheng Ming Tao; Nitin Mantri; Chuan Yin Fan; Xiao Qing Bao (Genetic Resources and Crop Evolution, 2014)

Multimineral optimization processing method based on elemental capture spectroscopy logging - Zhou Feng; Xin-Tong Li; Hong-Liang Wu; Shou-Ji Xia; Ying-Ming Liu (Applied Geophysics, 2014)

Synthesis and antibacterial evaluation of furan derivatives bearing a rhodanine moiety - Jian Che; Chang-Ji Zheng; Ming-Xia Song; Ya-Jing Bi; Yi Liu; Yin-Jing Li; Yan Wu; Liang-Peng Sun; Hu-Ri Piao (Medicinal Chemistry Research, 2014)

Supramolecular Interaction of Two Tryptophans with p-sulfonated calix[4,6,8]arene - Tao-Tao Pang; Hai-Long Liu; Li-Ming Du; Yin-Xia Chang; Yun-Long Fu (Journal of Fluorescence, 2014)

The PpLTP1 Primary Allergen Gene is Highly Conserved in Peach and Has Small Variations in Other Prunus Species - Ying-tao Ma; Xiang Zhou; Zhong-shan Gao; Xiong-wei Li; Hui-juan Jia; Hong-xia Wu; Rang-jin Xie; Zhi-qiang Wang; Ming-liang Yu; Ke Cao; Shuang-jian Chen; Ying-hui Li; et al. (Plant Molecular Biology Reporter, 2013)

Adsorption of nitrogen and phosphorus by intact cells and cell wall polysaccharides of Microcystis - Shan-Shan Li; Jian-Hong Li; Ming-Sheng Xia; Yan-Yan Meng; Hui Zhang (Journal of Applied Phycology, 2013)

Synthesis and potential antibacterial activity of new rhodanine-3-acetic acid derivatives - Jing Miao; Chang-Ji Zheng; Liang-Peng Sun; Ming-Xia Song; Li-Li Xu; Hu-Ri Piao (Medicinal Chemistry Research, 2013)

In vitro mutagenesis and directed screening for salt-tolerant mutants in peanut - Ming-Xia Zhao; Hai-Yan Sun; Rui-Rui Ji; Xiao-Hui Hu; Jiong-Ming Sui; Li-Xian Qiao; Jing Chen; Jing-Shan Wang (Euphytica, 2013)

Synthesis and evaluation in vitro of 1-[2-(10-dihydroartemisininoxy) ethyl]-3-phenylurea derivatives as potential agents against cancer - Wei Luo; Ming-yu Xia; Takashi Ikejima; Li-hua Li; Chun Guo (Medicinal Chemistry Research, 2013)

Effects of L-arginine and Nω-nitro-L-arginine methylester on learning and memory and α7 nAChR expression in the prefrontal cortex and hippocampus of rats - Xiao-Ming Wei; Wei Yang; Li-Xia Liu; Wen-Xiu Qi (Neuroscience Bulletin, 2013)

Quantification of serum HBXAP DNA in lung cancer patients by quantitative fluorescent polymerase chain reaction - Yu-Lei Hou; Hui Chen; Ming-Jian Ge; Feng-Zeng Li; Cheng-Jun Xue; Yan-Feng Wu; Hai-Xia Luo (Molecular Biology Reports, 2013)

Sonic Hedgehog (Shh) Regulates the Expression of Angiogenic Growth Factors in Oxygen–Glucose-Deprived Astrocytes by Mediating the Nuclear Receptor NR2F2 - Yanan Li; Yuanpeng Xia; Yong Wang; Ling Mao; Yuan Gao; Quanwei He; Ming Huang; Shengcai Chen; Bo Hu (Molecular Neurobiology, 2013)

Astrocyte-Derived Sonic Hedgehog Contributes to Angiogenesis in Brain Microvascular Endothelial Cells via RhoA/ROCK Pathway After Oxygen–Glucose Deprivation - Quan-Wei He; Yuan-Peng Xia; Sheng-Cai Chen; Yong Wang; Ming Huang; Yan Huang; Jian-Yong Li; Ya-Nan Li; Yuan Gao; Ling Mao; Yuan-Wu Mei; Bo Hu (Molecular Neurobiology, 2013)

Oxidative decarboxylation of mandelic acid derivative by recombinant Escherichia coli: a novel method of ethyl vanillin synthesis - Xiao-xia Pan; Jing-jing Li; Mei-gui Wang; Wen-sen He; Cheng-sheng Jia; Xiao-ming Zhang; Biao Feng; Da-li Li; Zeng Zeng (Biotechnology Letters, 2013)

Succession of plant and soil microbial communities with restoration of abandoned land in the Loess Plateau, China - Jun-Jian Li; Yuan-Ming Zheng; Jun-Xia Yan; Hong-Jian Li; Ji-Zheng He (Journal of Soils and Sediments, 2013)

Acute Clenbuterol Induces Hypotension, Atrioventricular Block and Cardiac Asystole in the Rabbit - Yan Ke; Li-Lan Fu; Xia-Fei Hong; Run Dong; Tian-Ming Xu; Jing-Fei Guo; Yan Liu; Ji-Min Cao (Cardiovascular Toxicology, 2013)

Competitive adsorption and desorption of oxytetracycline and cadmium with different input loadings on cinnamon soil - Yan-yu Bao; Ying Wan; Qi-xing Zhou; Wei-ming Li; Yu-xia Liu (Journal of Soils and Sediments, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Griffithsin inhibits Japanese encephalitis virus infection in vitro and in vivo - Hassan Z. A. Ishag; Chen Li; Li Huang; Ming-xia Sun; Fengjuan Wang; Bo Ni; Thowaiba Malik; Pu-yan Chen; Xiang Mao (Archives of Virology, 2013)

Association of CASP9, CASP10 gene polymorphisms and tea drinking with colorectal cancer risk in the Han Chinese population - He Liu; Xia Jiang; Ming-wu Zhang; Yi-feng Pan; Yun-xian Yu; Shan-chun Zhang; Xin-yuan Ma; Qi-long Li; Kun Chen (Journal of Zhejiang University-SCIENCE B, 2013)

Preparation, Structure and Near-infrared Luminescent Property of Yb(III) Complex with 2,4,6-Pyridinetricarboxylic Acid - Hong-Sheng Wang; Gong-Chun Li; Jun Xia; Bin Zhai; Ming-Li Liu (Journal of Fluorescence, 2013)

Synthesis, crystal structure and biological activity of novel anthranilic diamide insecticide containing alkyl ether group - Yu Zhao; Li-ping Xu; Jun Tong; Yong-qiang Li; Li-xia Xiong; Fang Li; Li-na Peng; Zheng-ming Li (Molecular Diversity, 2012)

Association of 10q23 with colorectal cancer in a Chinese population - Fen-Xia Li; Xue-Xi Yang; Xuan-Qiu He; Ni-Ya Hu; Ying-Song Wu; Ming Li (Molecular Biology Reports, 2012)

Migration of natural estrogens around a concentrated dairy-feeding operation - Yan-xia Li; Wei Han; Ming Yang; Cheng-hong Feng; Xiao-fei Lu; Feng-song Zhang (Environmental Monitoring and Assessment, 2012)

Improvement of myocardial glycolipid metabolic disorder in diabetic hamster with Astragalus polysaccharides treatment - Wei Chen; Yan-Ping Xia; Wen-Jie Chen; Mao-Hua Yu; Yi-Ming Li; Hong-Ying Ye (Molecular Biology Reports, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Inhibition of matrine against gastric cancer cell line MNK45 growth and its anti-tumor mechanism - Cong Luo; Hai Jun Zhong; Li Ming Zhu; Xian Guo Wu; Jie Er Ying; Xiao Hong Wang; Wang Xia LÜ; Qi Xu; Yong Liang Zhu; Jian Huang (Molecular Biology Reports, 2012)

VEGF is essential for the growth and migration of human hepatocellular carcinoma cells - Lei Zhang; Jia-Ning Wang; Jun-Ming Tang; Xia Kong; Jian-Ye Yang; Fei Zheng; Ling-Yun Guo; Yong-Zhang Huang; Li Zhang; Lin Tian; Shu-Fen Cao; Chang-Hai Tuo; et al. (Molecular Biology Reports, 2012)

Synthesis, structure, and biological activity of novel (oxdi/tri)azoles derivatives containing 1,2,3-thiadiazole or methyl moiety - Xing-Hai Liu; Li Pan; Jian-Quan Weng; Cheng-Xia Tan; Yong-Hong Li; Bao-Lei Wang; Zheng-Ming Li (Molecular Diversity, 2012)

Pt and Pd in sediments from the Pearl River Estuary, South China: background levels, distribution, and source - Li-feng Zhong; Wen Yan; Jie Li; Xiang-lin Tu; Bao-ming Liu; Zhen Xia (Environmental Science and Pollution Research, 2012)

Dynamics and functions of CD4+CD25high regulatory T lymphocytes in Chinese rhesus macaques during the early stage of infection with SIVmac239 - Shao-You Li; Hou-Jun Xia; Zheng-Xi Dai; Gao-Hong Zhang; Bo Fan; Ming-Hua Li; Rui-Rui Wang; Yong-Tang Zheng (Archives of Virology, 2012)

Pseudonocardia yuanmoensis sp. nov., a novel actinobacterium isolated from soil in Yunnan, south-west China - Guo-Xing Nie; Hong Ming; Da-Qiao Wei; En-Min Zhou; Xia Tang; Juan Cheng; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Effect of long-term administration of dietary β-1,3-glucan on growth, physiological, and immune responses in Litopenaeus vannamei (Boone, 1931) - Hong-Xia Zhao; Jun-Ming Cao; An-Li Wang; Zhen-Yu Du; Chao-Xia Ye; Yan-Hua Huang; Han-Bing Lan; Ting-Ting Zhou; Guo-Li Li (Aquaculture International, 2012)

Type 17 T-helper cells might be a promising therapeutic target for osteoporosis - Feng-Lai Yuan; Xia Li; Wei-Guo Lu; Yi-Qing Zhao; Cheng-Wan Li; Jian-Ping Li; Jun-Ming Sun; Rui-Sheng Xu (Molecular Biology Reports, 2012)

Isolation and identification of an acetoin high production bacterium that can reverse transform 2,3-butanediol to acetoin at the decline phase of fermentation - Xian Zhang; Tao-wei Yang; Qing Lin; Mei-juan Xu; Hai-feng Xia; Zheng-hong Xu; Hua-zhong Li; Zhi-ming Rao (World Journal of Microbiology and Biotechnology, 2011)

A risk-associated single nucleotide polymorphism of SMAD7 is common to colorectal, gastric, and lung cancers in a Han Chinese population - Xin Li; Xue-xi Yang; Ni-ya Hu; Jing-zhe Sun; Fen-xia Li; Ming Li (Molecular Biology Reports, 2011)

Development and application of a set of breeder-friendly SNP markers for genetic analyses and molecular breeding of rice (Oryza sativa L.) - Haodong Chen; Hang He; Yanjiao Zou; Wei Chen; Renbo Yu; Xia Liu; Yang Yang; Yong-Ming Gao; Jian-Long Xu; Liu-Min Fan; Yi Li; Zhi-Kang Li; et al. (Theoretical and Applied Genetics, 2011)

A double-blind, placebo-controlled study of traditional Chinese medicine sarsasapogenin added to risperidone in patients with negative symptoms dominated schizophrenia - Shi-Fu Xiao; Hai-Bo Xue; Xia Li; Chao Chen; Guan-Jun Li; Cheng-Mei Yuan; Ming-Yuan Zhang (Neuroscience Bulletin, 2011)

Phylogenetic analysis of the E2 gene of classical swine fever virus from the Guangxi Province of southern China - Ting Rong Luo; Su-huan Liao; Xian-shi Wu; Li Feng; Zhao-Xia Yuan; Hui Li; Jing-Jing Liang; Xian-Ming Meng; Hong-Yun Zhang (Virus Genes, 2011)

Rice Gene OsDSR-1 Promotes Lateral Root Development in Arabidopsis Under High-Potassium Conditions - Xu Ming Yin; Pedro S. C. F. Rocha; Man Ling Wang; Yu Xin Zhu; Luo Ye Li; Shu Feng Song; Xinjie Xia (Journal of Plant Biology, 2011)

Presence and Determination of Manure-borne Estrogens from Dairy and Beef Cattle Feeding Operations in Northeast China - Han Wei; Li Yan-xia; Yang Ming; Li Wei (Bulletin of Environmental Contamination and Toxicology, 2011)

Three new fatty acids from the roots of Boehmeria nivea (L.) Gaudich and their antifungal activities - Qiong-Ming Xu; Yan-Li Liu; Xiao-Ran Li; Xia Li; Shi-Lin Yang (Natural Product Research, 2011)

Comparison of Non-covalent Interactions Between a Series of N-Phosphoryl Dipeptide or Methyl Esters and Protein by Electrospray Ionization Mass Spectrometry - Li-ming Qiang; Ming-xiu Lü; Xu-ru Dong; Shu-xia Cao; Kui Lu; Yu-fen Zhao (International Journal of Peptide Research and Therapeutics, 2011)

Differential expression of expressed sequence tags in alfalfa roots under aluminum stress - Fu Fan; Xin-Wei Li; Yue-Ming Wu; Zhuo-Sheng Xia; Jin-Jun Li; Wen Zhu; Jin-Xin Liu (Acta Physiologiae Plantarum, 2011)

Mapping quantitative trait loci for seed size traits in soybean (Glycine max L. Merr.) - Yu Xu; He-Nan Li; Guang-Jun Li; Xia Wang; Li-Guo Cheng; Yuan-Ming Zhang (Theoretical and Applied Genetics, 2011)

Polymorphism of prion protein gene in sheep of Inner Mongolian, China - Cai-Xia Han; Hong-Xiang Liu; Yi-Xin Lu; Ming-Xin Song; De-Ming Zhao; Xiang-Mei Zhou; Li-Feng Yang; Xiao-Yun Li (Virus Genes, 2011)

Dynamic Changes of Heme Oxygenase-1 in the Hippocampus of Rats After Acute Carbon Monoxide Poisoning - Li Guan; Yan-Lin Zhang; Tao Wen; Xi-Fu Wang; Ming-Xia Zhu; Jin-Yuan Zhao (Archives of Environmental Contamination and Toxicology, 2011)

A web-based platform for rice microarray annotation and data analysis - DiJun Chen; Fan Zhang; ChunHui Yuan; Jing Lu; Xia Li; Ming Chen (Science China Life Sciences, 2010)

Simulation of organic carbon dynamics at regional scale for paddy soils in China - Xue-Zheng Shi; Ru-Wei Yang; David C. Weindorf; Hong-Jie Wang; Dong-Sheng Yu; Yao Huang; Xian-Zhang Pan; Wei-Xia Sun; Li-Ming Zhang (Climatic Change, 2010)

Influence of 14-day hind limb unloading on isolated muscle spindle activity in rats - Xue Hong Zhao; Xiao Li Fan; Xin Ai Song; Su Di Wu; Jun Chan Ren; Ming Xia Chen (Journal of Muscle Research and Cell Motility, 2010)

Structural basis for the action of xyloglucan endotransglycosylases/hydrolases: Insights from homology modeling - Qin Xu; Xia Ye; Li-Yan Li; Zong-Ming Cheng; Hong Guo (Interdisciplinary Sciences: Computational Life Sciences, 2010)

Plant regeneration from in vitro leaves of the peach rootstock ‘Nemaguard’ (Prunus persica × P. davidiana) - Houcheng Zhou; Ming Li; Xia Zhao; Xiucai Fan; Aiguang Guo (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Effect of dietary protein reduction with synthetic amino acids supplementation on growth performance, digestibility, and body composition of juvenile Pacific white shrimp, Litopenaeus vannamei - Ming-Yan Huai; Yong-Jian Liu; Li-Xia Tian; Shi-Xi Deng; An-Long Xu; Wen Gao; Hui-Jun Yang (Aquaculture International, 2010)

Adsorption of lead(II) from aqueous solution onto Hydrilla verticillata - Ling-zhi Huang; Guang-ming Zeng; Dan-lian Huang; Li-feng Li; Peng-mian Huang; Chang-bin Xia (Biodegradation, 2009)

Identification of the flavin-dependent monooxygenase-encoding YUCCA gene family in Populus trichocarpa and their expression in vegetative tissues and in response to hormone and environmental stresses - Xia Ye; Byung-guk Kang; Lori D. Osburn; Yi Li; Cheng Zong-Ming (Max) (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

A cotton (Gossypium hirsutum) DRE-binding transcription factor gene, GhDREB, confers enhanced tolerance to drought, high salt, and freezing stresses in transgenic wheat - Shi-Qing Gao; Ming Chen; Lian-Qin Xia; Hui-Jun Xiu; Zhao-Shi Xu; Lian-Cheng Li; Chang-Ping Zhao; Xian-Guo Cheng; You-Zhi Ma (Plant Cell Reports, 2009)

The Pharmacology Study of a New Recombinant Human VEGF Receptor-Fc Fusion Protein on Experimental Choroidal Neovascularization - Ming Zhang; Dechao Yu; Chun Yang; Qingjie Xia; Wang Li; Bin Liu; Hong Li (Pharmaceutical Research, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Malassezia Folliculitis in China - Glenn S. Bulmer; Xiong Ming Pu; Li Xia Ti Yi (Mycopathologia, 2008)

Characterization of tomato zonate spot virus, a new tospovirus in China - Jia-Hong Dong; Xiao-Fei Cheng; Yue-Yan Yin; Qi Fang; Ming Ding; Ting-Ting Li; Li-Zhen Zhang; Xiao-Xia Su; Jenifer Huang McBeath; Zhong-Kai Zhang (Archives of Virology, 2008)

Purification and characterization of a thermostable uricase from Microbacterium sp. strain ZZJ4-1 - Lei Kai; Xiao-Hang Ma; Xue-Lai Zhou; Xiao-Ming Jia; Xia Li; Kang-Ping Guo (World Journal of Microbiology and Biotechnology, 2008)

Isolation and molecular characterization of the Triticum aestivum L. ethylene-responsive factor 1 (TaERF1) that increases multiple stress tolerance - Zhao-Shi Xu; Lan-Qin Xia; Ming Chen; Xian-Guo Cheng; Rui-Yue Zhang; Lian-Cheng Li; Yun-Xiang Zhao; Yan Lu; Zhi-Yong Ni; Li Liu; Zhi-Gang Qiu; You-Zhi Ma (Plant Molecular Biology, 2007)

Proteomic identification of differently expressed proteins responsible for osteoblast differentiation from human mesenchymal stem cells - Ai-Xia Zhang; Wei-Hua Yu; Bao-Feng Ma; Xin-Bing Yu; Frank Fuxiang Mao; Wei Liu; Jia-Qing Zhang; Xiu-Ming Zhang; Shu-Nong Li; Ming-Tao Li; Bruce T. Lahn; Andy Peng Xiang (Molecular and Cellular Biochemistry, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

A stable and differentiable RNA positive control for reverse transcription-polymerase chain reaction - Ji-Ming Chen; Li-Xia Guo; Cheng-Ying Sun; Ying-Xue Sun; Ji-Wang Chen; Lin Li; Zhi-Liang Wang (Biotechnology Letters, 2006)

Determination of Trace Mercury by Solid Substrate-Room Temperature Phosphorimetry Quenching Method Based on Catalytic Effect of Hg2+on Formation of the Ion Association Complex [Sn(XO)6]4+·[(Fin)4] - Jia-Ming Liu; Ruo-Hong Wu; De-Chang Li; Ping Zhou; Min-Min Zheng; Xiao-Yi Zeng; Dong-Xia Liu; Xiao-Mei Huang; Guo-Hui Zhu (Journal of Fluorescence, 2006)

Purification, enzymatic properties of a recombinant d-hydantoinase and its dissociation by zinc ion - Ya-Wei Shi; Li-Xi Niu; Xia Feng; Jing-Ming Yuan (World Journal of Microbiology and Biotechnology, 2006)

The influence of feeding rate on growth, feed efficiency and body composition of juvenile grass carp (Ctenopharyngodon idella) - Zhen-Yu Du; Yong-Jian Liu; Li-Xia Tian; Jian-Guo He; Jun-Ming Cao; Gui-Ying Liang (Aquaculture International, 2006)

Detection of Two Fungal Biocontrol Agents against Root-knot Nematodes by RAPD Markers - Ming Liang Zhu; Ming He Mo; Zhen Yuan Xia; Yun Hua Li; Shu Jun Yang; Tian Fei Li; Ke Qin Zhang (Mycopathologia, 2006)

Outbreak of Trichophyton verrucosum in China Transmitted from Cows to Humans - Pu Xiong Ming; Yi Li Xia Ti; Glenn S. Bulmer (Mycopathologia, 2006)

Characterization of a bioflocculant from a newly isolated Vagococcus sp. W31 - Jie Gao; Hua-ying Bao; Ming-xiu Xin; Yuan-xia Liu; Qian Li; Yan-fen Zhang (Journal of Zhejiang University-SCIENCE B, 2006)

Litterfall Dynamics of an Evergreen Broadleaf Forest and a Pine Forest in the Subtropical Region of China - Zhi An Li; Bi Zou; Han-ping Xia; Hai Ren; Jiang-ming Mo; Hong Weng (Forest Science, 2005)
Monthly litterfall was monitored over a 10-year period from an evergreen broadleaf forest (EBF) and a pine forest (PF) in subtropical South China. During this period, litter was also collected bimonthly from the forest floor for 2 years. Total annual litterfall in EBF fluctuated around 9 Mg ha−1 with leaves, branches, and miscellanea accounting for 52.5%, 22.2%, and 25.3%, respectively. Total annual litterfall alternated between high and low values in consecutive years. Storms and pest outbreaks were responsible for most of the peaks in both monthly and annual litterfall. Litter from each of 43 species was recorded, but 9 species contributed about 85% of total litterfall. Dominant species shed their leaves in a more regular pattern with peaks mainly from Jan. to Mar. Pine forest (Pinus massoniana) produced much less litterfall than EBF, with a mean of 2.7 Mg ha−1. Here, leaves accounted for 73.2% of total litterfall, branches only 11.4%, and miscellanea 15.4%. Litter on the ground amounted to 5.2 Mg ha−1 in EBF and 2.9 Mg ha−1 in PF. The results show that this climax forest has much higher litterfall and forest floor mass than the pine forest, and litterfall is rather stable with regard to annual variation. FOR. SCI. 51(6):608–615.

Soil CO2 efflux and fungal and bacterial biomass in a plantation and a secondary forest in wet tropics in Puerto Rico - Yiqing Li; Ming Xu; Xiaoming Zou; Yang Xia (Plant and Soil, 2005)

Mapping of quantitative trait loci (QTLs) for rice protein and fat content using doubled haploid lines - Zhong-Li Hu; Ping Li; Ming-Quan Zhou; Zhi-Hong Zhang; Ling-Xia Wang; Li-Huang Zhu; Ying-Guo Zhu (Euphytica, 2004)

Bioluminescence of Aequorea macrodactyla, a Common Jellyfish Species in the East China Sea - Ning-Shao Xia; Wen-Xin Luo; Jun Zhang; Xiao-Yan Xie; Hai-Jie Yang; Shao-Wei Li; Ming Chen; Mun-Hon Ng (Marine Biotechnology, 2002)

A study of the surface-emerging palaeochannels on the South Coast Plain of Laizhou Bay - Mei Han; Dao-gao Li; Ming-hua Zhao; Ai-xia Jiang (Chinese Geographical Science, 2000)